Perovskite thin film, perovskite battery, preparation method and power utilization device

By designing a non-smooth structure on the surface of the perovskite film, including the inclined groove, the problem of low photon utilization of perovskite solar cells is solved, and the short-circuit current density and photoelectric conversion efficiency are improved.

CN119923177APending Publication Date: 2025-05-02CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311435162.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There is room for improvement in the short-circuit current density and photoelectric conversion efficiency of existing perovskite solar cells, especially because the photon utilization rate caused by smooth surfaces is not high.

Method used

A perovskite film is designed, with at least one side surface having a non-smooth surface and comprising a plurality of grooves. The sides of the concave groove are inclined at an inclined angle relative to the film thickness direction, increasing the contact opportunity between the photon and the film and increasing the light secondary incident ratio.

Benefits of technology

By increasing the contact opportunity between photons and perovskite films, the utilization rate of light is improved, and the short-circuit current density and photoelectric conversion efficiency of perovskite batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923177A_ABST
    Figure CN119923177A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite thin film, a perovskite battery, a preparation method and a power utilization device. The thickness direction of the perovskite thin film is recorded as the longitudinal direction, the perovskite thin film is provided with two opposite surfaces along the longitudinal direction, at least one surface is a non-smooth surface, and the non-smooth surface is provided with a plurality of concave grooves; at least a portion of the side surface of the concave groove is at an inclined angle with respect to the longitudinal direction. The perovskite thin film can be used as a light absorption layer in a perovskite battery, and the comprehensive performance of short-circuit current density and photoelectric conversion efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to perovskite films, perovskite cells, preparation methods and electrical devices. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] Perovskite solar cells (PSCs) are devices that convert solar energy into electrical energy using the photoelectric conversion mechanism of perovskite crystal materials. They are currently the third generation of solar cells and have many advantages, including high photoelectric conversion efficiency, simple manufacturing processes, and low production costs. They have been the subject of extensive research in recent years. Among these, improving the short-circuit current density (Jsc) and photoelectric conversion efficiency (PCE) to enhance the overall performance of these devices is a key research direction. Summary of the Invention

[0004] In view of the above problems, the present application provides a perovskite film, a perovskite cell, a preparation method, and an electrical device. The perovskite film can be used as a light-absorbing layer of a perovskite cell, thereby improving the combined performance of short-circuit current density (Jsc) and photoelectric conversion efficiency (PCE).

[0005] In a first aspect, the present application provides a perovskite film, wherein the thickness direction of the perovskite film is recorded as a longitudinal direction, and the perovskite film has two surfaces that are separated from each other along the longitudinal direction, at least one of which is a non-smooth surface, and the non-smooth surface is provided with a plurality of grooves;

[0006] At least a portion of the side surfaces of the concave groove are inclined at an angle relative to the longitudinal direction.

[0007] At least one side surface of the perovskite film is set as a non-smooth surface, and a concave groove is set in at least a part of the non-smooth surface. At this time, a groove-shaped long strip concave portion is introduced on the surface of the film, so that at least a part of the side surface of the concave groove is inclined at an angle relative to the longitudinal direction. By utilizing the reflection effect of the side surface of these concave portions on the incident light, the contact opportunity between photons and the perovskite film at the concave groove interface can be increased, the secondary incidence ratio of light can be improved, thereby increasing the total amount of light entering the perovskite film, increasing the utilization rate of the incident light, and further improving the comprehensive performance of the short-circuit current density and photoelectric conversion efficiency of the perovskite battery.

[0008] Based on any suitable embodiment of the present application, in some further embodiments, the surface roughness of the non-smooth area formed by at least a portion of the concave grooves is greater than or equal to 100 nm.

[0009] Optionally, the surface roughness of the non-smooth area formed by at least a portion of the concave grooves is 100 nm to 250 nm;

[0010] Optionally, the surface roughness is obtained by testing using a step profiler method.

[0011] The distribution of grooves on the surface of the perovskite film can affect the surface roughness of the perovskite film. By controlling the surface roughness of the non-smooth region within the above range, the grooves can be controlled to have a more suitable morphology, which helps to fully utilize the grooves' light capture effect and further improve the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0012] Based on any suitable embodiment in the present application, in some further embodiments, the sum of the areas of the concave grooves on the non-smooth surface is greater than or equal to 10% of the area of ​​the non-smooth surface, and can be optionally greater than or equal to 30%, and can further be optionally greater than or equal to 50%.

[0013] By adjusting the area ratio of the concave grooves on the surface of the perovskite film, the amount of light captured by the concave grooves can be adjusted. By controlling the percentage of the sum of the projected areas of the concave grooves along the thickness direction of the film relative to the area of ​​the non-smooth surface where the concave grooves are located within the above range, it is beneficial to more fully exert the light capture effect of the concave grooves, and more beneficial to improve the comprehensive performance of short-circuit current density and photoelectric conversion efficiency. When the proportion of the concave grooves reaches a certain level, the non-smooth surface can be made wrinkled. At this time, the lateral size combination of the concave grooves and the raised areas between the concave grooves is more matched, and the distribution of the concave grooves on the surface of the perovskite film is relatively uniform as a whole, which can absorb a large amount of incident light and more fully exert the light capture effect of the concave grooves.

[0014] Based on any suitable embodiment of the present application, in some further embodiments, the concave groove satisfies one or more of the following characteristics:

[0015] The aspect ratio of at least a portion of the concave grooves is greater than 1. Optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 2. Further, optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 3. Even further, optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 5.

[0016] The width of at least a portion of the concave grooves is less than or equal to 1.2 μm, and may be 0.5 μm to 1.2 μm, or further may be 0.6 μm to 1.1 μm.

[0017] The half-height width of at least a portion of the concave grooves is less than or equal to 1 μm, and can be optionally 0.2 μm to 0.6 μm;

[0018] The depth of at least a portion of the concave grooves is greater than or equal to 100 nm, and may be 100 nm to 500 nm, and may further be 100 nm to 250 nm.

[0019] The aspect ratio of at least a portion of the concave grooves is 0.08 to 0.5, optionally 0.1 to 0.5, and further optionally 0.1 to 0.3.

[0020] Based on any suitable embodiment of the present application, in some further embodiments, the concave groove satisfies one or more of the following characteristics:

[0021] In at least a portion of the non-smooth surface, the average width of the concave grooves is 0.2 μm to 1 μm, optionally 0.5 μm to 1.2 μm, and further optionally 0.6 μm to 1.1 μm;

[0022] In at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.1 μm to 1 μm, and can be optionally 0.2 μm to 0.6 μm;

[0023] In at least a portion of the non-smooth surface, the average depth of the concave grooves is 100 μm to 500 nm, and can be optionally 100 nm to 250 nm;

[0024] In at least a portion of the non-smooth surface, the average aspect ratio of the concave grooves is 0.08 to 0.5, optionally 0.1 to 0.5, and further optionally 0.1 to 0.3.

[0025] By adjusting one or more of the groove's width, depth, aspect ratio, and the average of these parameters, the probability of photons being captured by the groove can be adjusted. By controlling one or more of these parameters within the aforementioned ranges, the groove's light capture effect is enhanced, thereby improving the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0026] Based on any suitable embodiment in the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average spacing of the grooves is 1 μm to 20 μm, and can be optionally 10 μm to 20 μm.

[0027] By adjusting the average spacing of the grooves, the density of the grooves in the perovskite film can be adjusted, thereby adjusting the number of grooves. Keeping the average spacing within the above range can fully utilize the aforementioned light-trapping function of the grooves, improving the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0028] Based on any suitable embodiment of the present application, in some further embodiments, the opening width of at least a portion of the concave grooves is greater than the bottom width;

[0029] Optionally, based on the projected area of ​​the concave grooves along the longitudinal direction, at least 50% of the opening widths of the concave grooves are greater than the bottom widths, and further optionally, at least 80% of the opening widths of the concave grooves are greater than the bottom widths;

[0030] Optionally, based on the projected area of ​​the concave groove along the longitudinal direction, the opening width of at least a portion of the concave grooves is greater than the half-height width and the bottom width; further optionally, the opening width of at least 50% of the concave grooves is greater than the half-height width and the bottom width; further optionally, the opening width of at least 80% of the concave grooves is greater than the half-height width and the bottom width.

[0031] When the concave groove has a cross-sectional shape that is wide at the top and narrow at the bottom, the opening width of the concave groove is greater than the bottom width, which is conducive to more incident light entering the concave groove, thereby improving the absorption of incident light by the perovskite film and increasing the amount of light captured by the concave groove, thereby better improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.

[0032] Based on any suitable embodiment of the present application, in some further embodiments, the concave groove satisfies one or more of the following characteristics:

[0033] At least a portion of the concave grooves have corners in their extending directions;

[0034] At least a portion of the concave grooves has a non-linear extension direction;

[0035] At least a portion of the concave grooves have intersection nodes.

[0036] When at least a portion of the concave grooves have one or more of the following characteristics in the extension direction: (1) there is a corner in the extension direction of at least a portion of the concave grooves; (2) at least a section of the length in the extension direction of at least a portion of the concave grooves is non-linear; and (3) at least a portion of the concave grooves have an intersection node; in this case, the concave grooves are more likely to be randomly distributed on the surface of the perovskite film, which is beneficial to shorten the distance from the contact interface to the capture of photons by the perovskite film, which is beneficial to improve the light capture efficiency, thereby helping to better improve the comprehensive performance of short-circuit current density and photoelectric conversion efficiency. Among them, the existence of intersection nodes in different concave grooves means that the extension directions of these different concave grooves are not parallel or not completely parallel, resulting in intersection, so that different concave grooves are connected.

[0037] Based on any suitable embodiment in the present application, in some further embodiments, the perovskite film includes a titanite-type metal halide, and the halogen in the perovskite-type metal halide includes bromine and iodine.

[0038] According to the composition design of perovskite metal halide in perovskite film, bromine and iodine elements can be set simultaneously in the perovskite precursor solution. By adjusting the ratio of the two elements, multiple parameters such as the size-related parameters of the grooves (such as length, width, depth, aspect ratio and the average value of any of the foregoing) and distribution-related parameters (such as average spacing, the proportion of the groove area on the perovskite film surface, the surface roughness of the perovskite film, etc.) can be controlled, thereby flexibly adjusting the comprehensive enhancement effect of the grooves on the short-circuit current density and photoelectric conversion efficiency.

[0039] Based on any suitable embodiment of the present application, in some further embodiments, the atomic molar ratio of bromine and iodine in the perovskite metal halide is (3-y):y, wherein 0 <y≤1.2;

[0040] Optionally, 0.6≤y≤1.2.

[0041] According to the composition design of perovskite metal halide in perovskite film, the atomic molar ratio of bromine and iodine in the perovskite precursor solution can be adjusted to improve the comprehensive performance of short-circuit current density and photoelectric conversion efficiency of perovskite battery.

[0042] Based on any suitable embodiment in the present application, in some further embodiments, the band gap of the perovskite film is 1.4 eV to 2.0 eV, and can be optionally 1.6 eV to 1.8 eV.

[0043] When the titanium ore film has the above-mentioned band gap, it is beneficial to improve the power density of the device, and combined with the aforementioned concave groove design, it is beneficial to achieve better overall performance of the device.

[0044] Based on any suitable embodiment in the present application, in some further embodiments, at least a portion of the perovskite grains in the perovskite film are through-type grains, and the two ends of the through-type grains along the longitudinal direction are respectively located on both side surfaces of the perovskite film.

[0045] When the perovskite grains in a perovskite film include through-type grains along the thickness direction of the perovskite film (i.e., along the longitudinal direction), it means that these perovskite grains grow continuously in the longitudinal direction, with few cracks in the longitudinal cross-section of the perovskite film, and appear as large-sized grains that penetrate the film longitudinally. In this case, the through-type grains that penetrate the perovskite film longitudinally facilitate smoother and more efficient carrier transmission, help reduce non-radiative recombination caused by grain interfaces, and improve the photoelectric conversion efficiency of the device.

[0046] Based on any suitable embodiment of the present application, in some further embodiments, the lateral size of at least a portion of the through-type grains is greater than or equal to 0.4 μm;

[0047] Optionally, a lateral dimension of at least a portion of the through-type grains is greater than or equal to 0.6 μm, optionally greater than or equal to 0.8 μm, and further optionally greater than or equal to 1 μm;

[0048] Optionally, the average lateral size of the through-type grains is 0.6 μm to 2 μm, and optionally 0.6 μm to 1.2 μm.

[0049] By controlling the lateral size of the through-grains, the number of interfaces between perovskite grains can be adjusted. A larger lateral size reduces the number of through-grains, resulting in fewer defects and higher-quality perovskite films. By controlling the lateral size of the through-grains within the aforementioned range, the positive effects of the through-grains can be fully utilized.

[0050] Based on any suitable embodiment in the present application, in some further embodiments, on the longitudinal cross-section of the perovskite film, the area percentage of the through-type grains with a lateral size greater than or equal to 1 μm relative to the longitudinal cross-section is greater than or equal to 30%, optionally greater than or equal to 40%, and further optionally greater than or equal to 50%.

[0051] By controlling the percentage of the area occupied by larger through-type grains in the longitudinal cross-section of the perovskite film, the role of the through-type grains can be adjusted. By controlling the area percentage of through-type grains of a certain lateral size relative to the longitudinal cross-section of the perovskite film within the above range, the advantages of the through-type grains can be more fully utilized, further promoting carrier transport and improving photoelectric conversion efficiency.

[0052] In a second aspect of the present application, a perovskite cell is provided, comprising the perovskite film according to the first aspect of the present application, wherein the non-smooth surface in the perovskite film forms a non-smooth interface with an adjacent structural layer.

[0053] Based on any suitable embodiment of the present application, in some further embodiments, the perovskite cell includes a first electrode, a first charge transport layer, a perovskite layer, a second charge transport layer, and a second electrode arranged in sequence;

[0054] Wherein, the perovskite layer is the perovskite film described in the first aspect of this application;

[0055] One of the first charge transport layer and the second charge transport layer is an electron transport layer, and the other is a hole transport layer;

[0056] At least one of the first electrode and the second electrode is a transparent electrode;

[0057] The non-smooth surface in the perovskite film faces away from one of the transparent electrodes.

[0058] In a third aspect of the present application, a method for preparing a perovskite battery is provided, comprising the following steps: sequentially stacking a first charge transport layer, a perovskite layer, a second charge transport layer, and a second electrode on a surface of one side of a first electrode to prepare the perovskite battery; wherein the perovskite layer is the perovskite film defined in the first aspect of the present application;

[0059] The method of stacking the perovskite layer on the side of the first charge transport layer facing away from the first electrode comprises the following steps:

[0060] Applying a precursor solution of the perovskite layer to a surface of the first charge transport layer facing away from the first electrode;

[0061] The precursor liquid is subjected to vacuum flash evaporation treatment and annealing treatment to form the perovskite layer, and the non-smooth surface is formed on a side of the perovskite layer away from the first electrode.

[0062] The vacuum flash evaporation process, used to prepare the perovskite layer, creates the aforementioned concave groove structure on at least one surface of the perovskite layer, increasing light utilization and improving the combined performance of the perovskite cell's short-circuit current density and photoelectric conversion efficiency. Furthermore, it promotes the formation of large, through-hole grains, boosting carrier transport and photoelectric conversion efficiency.

[0063] Based on any suitable embodiment of the present application, in some further embodiments, the solvent in the precursor solution of the perovskite layer includes N,N-dimethylformamide and dimethyl sulfoxide;

[0064] Optionally, the solvent in the precursor solution of the perovskite layer is a combination of N,N-dimethylformamide and dimethyl sulfoxide;

[0065] Optionally, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (2-6):1, and further optionally (3-5):1.

[0066] Based on any suitable embodiment of the present application, in some further embodiments, the preparation method meets one or more of the following characteristics:

[0067] The vacuum flash evaporation treatment is carried out under negative pressure conditions, wherein the pressure of the negative pressure conditions is less than or equal to 100 Pa, and can be selected from 50 Pa to 100 Pa;

[0068] The duration of the vacuum flash evaporation treatment is 15s to 100s, and can be optionally 20s to 60s;

[0069] The temperature for the vacuum flash evaporation treatment is 10°C to 40°C, and can be optionally 20°C to 30°C;

[0070] The annealing treatment is performed using a hot plate, optionally using a hot plate at 90°C to 110°C, further optionally using a hot plate at 95°C to 105°C;

[0071] The annealing time for the annealing treatment is 5 minutes to 20 minutes, and can be optionally 8 minutes to 12 minutes.

[0072] Based on any suitable embodiment of the present application, in some further embodiments, the coating method in the step of coating the precursor solution of the perovskite layer onto the surface of the first charge transport layer on the side away from the first electrode is spin coating;

[0073] Optionally, the spin coating speed is 2000 rpm to 6000 rpm, and optionally 2000 rpm to 4000 rpm.

[0074] By adjusting one or more parameters in the perovskite layer preparation process and regulating the grain size and surface morphology of the perovskite layer as needed, the comprehensive performance of the short-circuit current density and photoelectric conversion efficiency of the perovskite battery can be better improved through process parameter optimization.

[0075] In the fourth aspect of the present application, an electrical device is provided, which includes at least one of the perovskite film described in the first aspect of the present application, the perovskite battery described in the second aspect of the present application, and the perovskite battery prepared by the preparation method described in the third aspect of the present application.

[0076] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] In order to better describe and illustrate the embodiments or examples of the applications disclosed herein, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered to limit the scope of the disclosed applications, the embodiments or examples currently described, and any of the best modes currently understood for these applications. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0078] Figure 1 This is an optical microscope image of the surface morphology of the perovskite film prepared by the vacuum flash evaporation method in one embodiment of the present application.

[0079] Figure 2 This is a comparison chart of the surface roughness test of the perovskite film prepared in an embodiment of the present application and a comparison. Among them, the vacuum flash evaporation method corresponds to the embodiment, and the anti-solvent method corresponds to the comparison. Figure 2 The horizontal axis in FIG is the horizontal trajectory (from 0 μm to 40 μm), indicating the test path along the horizontal direction.

[0080] Figure 3 This is a volt-ampere characteristic curve of the perovskite film prepared by vacuum flash evaporation in one embodiment of the present application.

[0081] Figure 4 These are scanning electron microscope (SEM) images of a perovskite film prepared by vacuum flash evaporation in one embodiment of the present application, wherein (A) is a longitudinal cross-sectional view and (B) is a transverse cross-sectional view.

[0082] Figure 5 These are scanning electron microscope (SEM) images of the perovskite film prepared by the anti-solvent method in a comparative example of this application, wherein (A) is a longitudinal cross-sectional view and (B) is a transverse cross-sectional view.

[0083] Figure 6 This is a statistical bar chart of the grain sizes of perovskite films prepared in one embodiment (a) and a comparative example (b) of the present application, reflecting the number of perovskite film grains of different sizes; wherein, a is an embodiment, using the vacuum flash evaporation method; b is a comparative example, using the anti-solvent method; the number of grains of different grain sizes is counted based on the maximum diameter of the perovskite film grains within the statistical range.

[0084] Figure 7 This is a schematic diagram of a perovskite cell according to one embodiment of the present application; it includes a substrate layer, a first electrode, a first charge transport layer, a perovskite layer, a second charge transport layer and a second electrode.

[0085] Figure 8 Schematic diagram of a perovskite cell according to one embodiment of the present application.

[0086] Figure 9 Schematic diagram of an electrical device in which the perovskite cell according to one embodiment of the present application is used as a power generation device.

[0087] Explanation of the figure numbers: 100 is a perovskite cell; 110 is a substrate layer; 120 is a first electrode; 130 is a first charge transport layer; 140 is a perovskite layer; 150 is a second charge transport layer; 160 is a second electrode; P1 is a first etching area; P2 is a second etching area; P3 is a third etching area; 6 is an electrical device. DETAILED DESCRIPTION

[0088] Below, some embodiments of the perovskite film, perovskite battery, preparation method, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0089] " scope " disclosed in the present application can be limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if minimum range values ​​1 and 2 are listed, and if maximum range values ​​3,4 and 5 are also listed, then the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer greater than or equal to 2, this is equivalent to listing the parameter as, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and so on. For example, when a parameter is expressed as an integer selected from "2-10," this is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0090] In this application, terms such as "multiple," "multiple," "multiple items," and "several" refer to a quantity greater than or equal to two, unless otherwise specified. For example, "one or more" refers to one or greater than or equal to two items. It is understood that when "any number" of items is mentioned, it refers to any suitable combination of multiple items, that is, any combination of "any number" of items that is not conflicting and that can implement this application.

[0091] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0092] References to "embodiments" herein mean that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of such phrases in various locations in the specification does not necessarily refer to the same embodiment, nor does it necessarily refer to independent or alternative embodiments that are mutually exclusive with other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments. References to "implementations" herein have a similar understanding.

[0093] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which the steps are written does not imply a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, and may preferably be performed sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0094] In this application, in open technical features or technical solutions described with words such as "contain," "include," and "include," unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2, and a3. Unless otherwise specified, it may also include other members or not. It can be regarded as providing both the feature or solution of "A consists of a1, a2, and a3" or "A is selected from a1, a2, and a3", and the feature or solution of "A includes not only a1, a2, and a3, but also other members."

[0095] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0096] In this application, "optionally," "optional," and "optional" mean optional, that is, they refer to either option selected from the two parallel options of "yes" or "no." If multiple "options" appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "optional" is independent. Unless otherwise specified, the descriptions "optionally include," "optionally include," etc. in this application, using "optionally include" as an example, mean "may include or not include."

[0097] In this application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more relevant listed items, and also include any and all combinations of the relevant listed items, wherein the arbitrary and all combinations include any two relevant listed items, any more relevant listed items, or a combination of all relevant listed items. For example, "A and / or B" means a group consisting of A, B, and "a combination of A and B." Among them, "including A and / or B" can mean "including A, including B, and including A and B", and can also mean "including A, including B, or including A and B", which can be appropriately understood according to the sentence in which it is located.

[0098] As used herein, "combination thereof", "any combination thereof", "any combination thereof" and the like include all suitable combinations of any two or more of the listed items.

[0099] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc. shall be based on the technical solution that can implement the present application.

[0100] Herein, the terms "preferred," "better," "more preferred," and "suitable" are used solely to describe preferred implementations or examples and should not be construed as limiting the scope of protection of this application. If multiple "preferred" terms appear in a technical solution, each "preferred" term is considered independent unless otherwise specified and there are no contradictions or mutual constraints.

[0101] In this application, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of this application.

[0102] In this application, the terms "first," "second," "third," "fourth," etc. in "the first aspect," "the second aspect," "the third aspect," "the fourth aspect," etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or quantity, nor should they be understood as implicitly indicating the importance or quantity of the indicated technical features. Furthermore, "first," "second," "third," "fourth," etc. serve only as non-exhaustive enumeration and description, and should be understood not to constitute a closed-ended limitation on quantity.

[0103] In this application, the term "room temperature" generally refers to 4°C to 35°C, and may refer to 20°C ± 5°C. In some embodiments of this application, room temperature refers to 20°C to 30°C.

[0104] In this application, when describing a data range, if only the right endpoint is followed by the unit, it means that the units of the left and right endpoints are the same. For example, "3~5h" or "3-5h" both indicate that the units of the left endpoint "3" and the right endpoint "5" are both hours, and both have the same meaning as "3h~5h". This applies not only to time units, but also to unit descriptions of parameters such as temperature, size, and band gap.

[0105] The weights of the relevant components mentioned in the examples of this application may not only refer to the content of each component, but also represent the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the examples of this application, it is within the scope disclosed in the examples of this application. Furthermore, the weights mentioned in the examples of this application may be mass units known in the chemical industry, such as μg, mg, g, and kg.

[0106] In this application, "greater than or equal to" can be equivalently expressed as "≥", "less than or equal to" can be equivalently expressed as "≤", "greater than" can be equivalently expressed as ">", and "less than" can be equivalently expressed as "<". In this application, unless otherwise specified, "greater than or equal to" can be regarded as providing two solutions of "greater than" and "equal to". In this application, unless otherwise specified, "less than or equal to" can be regarded as providing two solutions of "less than" and "equal to".

[0107] In this application, exemplary descriptions such as "in some embodiments (or examples)" and "in one embodiment (or example)" may include but are not limited to the following meanings: these solutions can be combined with other solutions in a suitable manner to form new technical solutions.

[0108] As used herein, unless otherwise specified, "alkyl" refers to a monovalent residue resulting from the loss of a hydrogen atom from a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. Phrases containing this term, such as "C1-9 alkyl," refer to an alkyl group containing 1 to 9 carbon atoms, and each occurrence may independently be a C1 alkyl, a C2 alkyl, a C3 alkyl, a C4 alkyl, a C5 alkyl, a C6 alkyl, a C7 alkyl, a C8 alkyl, or a C9 alkyl group. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(C H3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (- CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH( )2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3 and octyl (-(CH2)7CH3).

[0109] In this article, unless otherwise specified, "aryl" refers to an aromatic hydrocarbon group derived from an aromatic hydrocarbon compound by losing a hydrogen atom, that is, a monovalent linking site formed directly on the ring. It can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic aromatic groups, at least one is an aromatic ring system. For example, "C6-C 10 "Aryl" refers to an aromatic group containing 6 to 10 carbon atoms, each occurrence of which can be independently C6 aryl, C8 aryl, C9 aryl or C 10 Aryl. For example, "C6~C 20 "Aryl" refers to an aromatic group containing 6 to 20 carbon atoms, each occurrence of which can be independently but not limited to C6 arylaryl (such as phenyl), C6 arylaryl (such as benzocyclobutenyl), C8 aryl (such as phenylcyclobutenyl), C9 aryl (such as indenyl), C 10 Aryl (such as naphthyl), C 12 Aryl (such as acenaphthenyl, biphenyl), C 13 Aryl (such as fluorenyl), C 14 Aryl (such as anthracenyl, phenanthrenyl), C 18 Aryl (such as triphenylene) or C 20 Aryl (eg, perylene). Examples of suitable aromatic cyclic hydrocarbon compounds include, but are not limited to, benzene, stycyclobutene, biphenyl, indene, naphthalene, acenaphthene, fluorene, anthracene, phenanthrene, triphenylene, perylene, and derivatives thereof.

[0110] The antisolvent method is a common method for preparing perovskite thin films, commonly used to prepare small-area wide-bandgap perovskite solar cells. However, the antisolvent method involves the addition of an antisolvent, which is susceptible to operator artifacts.

[0111] Without adopting special control strategies, the surfaces on both sides of the perovskite film are usually smooth, and a portion of the incident light passes through the perovskite film without being utilized, resulting in poor light utilization.

[0112] To address the aforementioned common technical issues, the present application provides, in a first aspect, a perovskite film having at least one surface having a non-smooth surface including concave grooves. This perovskite film can be used to provide the perovskite layer in a perovskite cell, thereby improving the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0113] In this application, unless otherwise specified, "perovskite film" refers to a film containing a perovskite material that can be used as a light-absorbing layer in a solar cell. In this case, the solar cell can be referred to as a perovskite cell, and the corresponding light-absorbing layer can be referred to as a perovskite layer. Typically, the perovskite material includes a perovskite-type metal halide.

[0114] In this application, unless otherwise specified, the thickness direction of a perovskite film is referred to as the "longitudinal direction." Along the film's thickness direction, the perovskite film has two opposing surfaces, which can be referred to as the first surface and the second surface. The direction perpendicular to the longitudinal direction is referred to as the "transverse direction."

[0115] In this application, unless otherwise specified, a "non-smooth surface" of a perovskite film refers to a non-smooth area on the film surface, where the film surface within the non-smooth area has ups and downs along the thickness direction of the film, resulting in a certain degree of roughness on the film surface. In this application, the height difference that causes surface roughness in the non-smooth surface is generally greater than or equal to 100nm (≥100nm). For a non-smooth surface of a perovskite film, the vector direction pointing from the inside of the film to the non-smooth surface in the longitudinal direction is recorded as the "first direction."

[0116] In the present application, the "grooves" on the surface of the perovskite film refer to depressions with a certain depth along the thickness direction of the film. The grooves have a certain aspect ratio in the transverse direction, forming a long strip-shaped profile. The length direction of the long strip-shaped profile can be recorded as the extension direction of the grooves. An independent groove is not connected to any other grooves except for the two endpoints within its extended length; any endpoint can be a closed endpoint independently, or it can be connected to other grooves through an intersection node. In the present application, the "intersection node" of different grooves refers to the node formed by the intersection of different grooves in the extension direction. At the intersection node, the different grooves that intersect are connected. There is no special restriction on the trajectory shape of the extension direction of the grooves. It can be a straight line segment or an irregular line segment.

[0117] The "groove extension direction" refers to the lateral direction of the groove. The lateral direction of the groove can be determined by collecting the outer contour of the groove on the perovskite film surface and sequentially connecting the width centers of the outer contour at different lengths. The resulting line connecting the contour width centers can be used to characterize the groove's extension direction. This line connecting the contour width centers can be referred to as the "groove extension line." Within the groove's extended contour on the film surface, the length of the line connecting the groove's contour width centers can be referred to as the "groove length."

[0118] On a non-smooth surface with grooves, the "average groove spacing" can be determined by statistically analyzing the average distance between each extension line. For example, this can be determined by averaging the distances between each extension line at different sampling locations. The average groove spacing within a selected area can also be estimated using the following formula: A1 / L1, where A1 is the area of ​​the selected non-smooth area and L1 is the sum of the lengths of the extension lines of each groove within the selected non-smooth area.

[0119] The "longitudinal cross section of the concave groove" is a cross section perpendicular to the groove extension line and parallel to the film thickness direction. The contour line of this longitudinal cross section is an open line that opens at the top and concave downward. The position of the longitudinal cross section contour line close to the outer side of the film is denoted as the "top". The two upper endpoints of the longitudinal cross section contour line are connected by a line denoted as the "opening line". The length of this opening line is denoted as the "opening width of the concave groove" or "width of the concave groove". The position of the longitudinal cross section contour line farthest from the opening line is denoted as the "bottom of the concave groove". At this bottom, a straight line is drawn parallel to the opening line. The length of the line segment between this line and the longitudinal cross section contour line is denoted as the "bottom width of the concave groove". The vertical distance between each point on the longitudinal cross section contour line and the opening line corresponds to the depth of the concave groove at different contour positions. The maximum vertical distance is denoted as the "depth of the concave groove". At the midpoint of the maximum depth (i.e., halfway up), a straight line is drawn parallel to the opening line. The length of the line segment between this line and the longitudinal cross section contour line is denoted as the "half-height width of the concave groove".

[0120] The ratio of the length of the concave groove to the width of the concave groove is recorded as the "aspect ratio of the concave groove". Unless otherwise specified, the aspect ratio of the concave groove is greater than 1.

[0121] The ratio of the depth of the concave groove to the width of the concave groove is recorded as the "aspect ratio of the concave groove".

[0122] In this application, the shape parameters of the grooves on the surface of the perovskite film can be tested and analyzed using methods including but not limited to the following:

[0123] (1) Obtaining a topography or surface roughness curve of the perovskite film surface by scanning electron microscopy (SEM), optical microscopy, step profiler, etc., and combining with image analysis software such as Image-J to test and analyze the following information and / or parameters: including but not limited to the extension profile of the grooves on the perovskite film surface, the extension line of the grooves, the extension direction of the grooves, the length of the grooves, the average spacing of the grooves, the area of ​​the non-smooth area, etc.;

[0124] (2) Obtain a longitudinal cross-sectional view of the perovskite film by scanning electron microscopy (SEM), optical microscopy, and other methods, and the following information and / or parameters can be tested and analyzed in combination with image analysis software such as Image-J: longitudinal cross-section of the groove, contour line of the longitudinal cross-section, opening connection line, opening width of the groove, width of the groove, bottom width of the groove, depth of the groove, half-height width of the groove, aspect ratio of the groove, depth-to-width ratio of the groove, etc.;

[0125] (3) Average value: The average value of the average width, average half-height width, average depth, average depth-to-width ratio, average length, and average length-to-width ratio of the grooves can be obtained by collecting the corresponding parameter values ​​at multiple locations and performing a simple arithmetic average operation. The number of collection locations can be appropriately selected based on the level of differentiation of the groove shapes and sizes. For example, the minimum amount of data collection can be determined by controlling the standard deviation of the average value to be less than or equal to (≤) 10% of the average value. As a non-limiting example, the average width of the grooves can be obtained by collecting the width values ​​of the grooves at a suitable number (e.g., 20) locations, and the average value obtained by performing a simple arithmetic average operation can be used as the "average width of the grooves."

[0126] The method described in the following examples can be used to obtain a sample of a perovskite film to be tested. Taking SEM observation as an example, a thin film assembly in which a perovskite layer has been deposited on a hole transport layer but an electron transport layer has not yet been deposited is used as the sample to be tested. The following can be tested and analyzed in both the longitudinal and transverse directions: (1) The observation surface is the surface of one side of the perovskite layer; (2) The perovskite film sample is cut longitudinally using a glass knife, and the longitudinal cross section is placed upward for SEM testing; (3) The sample is sliced ​​longitudinally using a cryo-focused electron beam (FIB), and the resulting cross section is the longitudinal cross section, and the cross section is subjected to SEM morphology observation.

[0127] In some embodiments, a perovskite film is provided, wherein the thickness direction of the perovskite film is recorded as a longitudinal direction, and the perovskite film has two opposite surfaces along the longitudinal direction, wherein at least one surface is a non-smooth surface, and the non-smooth surface includes a plurality of concave grooves; at least a portion of the side surfaces of the concave grooves are inclined at an angle relative to the longitudinal direction.

[0128] It can be understood that due to the presence of the concave grooves, there are non-smooth areas in the non-smooth surface.

[0129] In the present application, unless otherwise specified, “at least a portion of the side surfaces of the concave groove are inclined at an angle relative to the longitudinal direction” means that at least a portion of the concave grooves meet the requirement that the widths at at least a portion of the depth positions are different.

[0130] At least one side surface of the perovskite film is set as a non-smooth surface, and a concave groove is set in at least a part of the non-smooth surface. At this time, a groove-shaped long strip concave portion is introduced on the surface of the film, so that at least a part of the side surface of the concave groove is inclined at an angle relative to the longitudinal direction. By utilizing the reflection effect of the side surface of these concave portions on the incident light, the contact opportunity between photons and the perovskite film at the concave groove interface can be increased, the secondary incidence ratio of light can be improved, thereby increasing the total amount of light entering the perovskite film, increasing the utilization rate of the incident light, and further improving the comprehensive performance of the short-circuit current density and photoelectric conversion efficiency of the perovskite battery.

[0131] Based on any suitable embodiment of the present application, in some further embodiments, the surface roughness of the non-smooth area formed by at least a portion of the concave grooves is ≥100 nm. Optionally, the surface roughness of the non-smooth area formed by at least a portion of the concave grooves is 100 nm to 250 nm. The surface roughness of the non-smooth area formed by at least a portion of the concave grooves can also be selected from any of the following values, or greater than or equal to any of the following values ​​(optionally less than or equal to 250 nm), or selected from an interval consisting of any two of the following values: 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 210 nm, 220 nm, 240 nm, 250 nm, etc.

[0132] In this application, unless otherwise specified, "surface roughness" refers to the surface unevenness caused by the alternating arrangement of micro- and nano-scale convex and concave features. A smaller surface roughness indicates a smoother surface; a larger surface roughness indicates a more uneven surface. In perovskite films, a greater surface roughness caused by concave grooves indicates a more uneven surface.

[0133] In this application, unless otherwise specified, the "surface roughness" of a perovskite film can be characterized by the distance between the highest and lowest points of a concave groove along the longitudinal direction. Generally, a "concave groove" is defined as the concave portion between two nearest protrusions with a height difference of 100 nm or greater between the highest and lowest points. Fluctuations less than 100 nm are considered topographical variations within the groove. Unless otherwise specified, the "surface roughness" of a specified area is numerically equal to the average depth of the concave grooves within the specified area.

[0134] The surface roughness of the selected non-smooth area can be measured using, but is not limited to, a step profiler. The step profiler can be a stylus profilometer. The groove dimensions can be statistically analyzed based on the surface roughness curve obtained from the test, as described in the Examples section below.

[0135] In some embodiments, the surface roughness is measured using a step profiler method.

[0136] The shape and dimensions of the grooves (e.g., length, width, depth, aspect ratio, length-to-depth ratio, depth-to-width ratio, etc.), as well as the distribution and pattern of the grooves on the surface of the perovskite film, can affect the surface roughness of the perovskite film. By controlling the surface roughness of the non-smooth regions of the non-smooth surface within the above range, the grooves can be controlled to have a more suitable morphology, which is conducive to more fully utilizing the grooves' light capture effect and further improving the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0137] Based on any suitable embodiment of the present application, in some further embodiments, on the non-smooth surface, the percentage ratio of the sum of the projected areas of the concave grooves along the longitudinal direction to the projected area of ​​the non-smooth surface along the longitudinal direction (which can be recorded as R1) is ≥10%, optionally ≥30%, and further optionally ≥50%. On the non-smooth surface, the percentage ratio of the sum of the projected areas of the concave grooves along the longitudinal direction to the projected area of ​​the non-smooth surface along the longitudinal direction can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from an interval consisting of any two of the following percentages: 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, etc. R1 can also be selected from any suitable range in the following ranges: 30% to 100%, 40% to 100%, 50% to 100%, 60% to 100%, 30% to 90%, 40% to 90%, 50% to 90%, 60% to 90%, 30% to 80%, 40% to 80%, 50% to 80%, 60% to 80%, 30% to 70%, 40% to 70%, 50% to 70%, 60% to 70%, 30% to 60%, 40% to 60%, 50% to 60%, etc.

[0138] “The percentage of the sum of the projected areas of the concave grooves along the longitudinal direction to the projected area of ​​the non-smooth surface along the longitudinal direction” may reflect the proportion of the concave grooves in the non-smooth surface.

[0139] The amount of light captured by the concave grooves can be adjusted by adjusting the percentage of the sum of the projected areas of the concave grooves along the longitudinal direction relative to the projected area of ​​the non-smooth surface along the longitudinal direction. By controlling the "percentage of the sum of the projected areas of the concave grooves along the thickness direction of the film relative to the projected area of ​​the non-smooth surface along the longitudinal direction where the concave grooves are located" within the above range, it is beneficial to more fully exert the light capture effect of the concave grooves and more conducive to improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency. When the proportion of the concave grooves reaches a certain level, the non-smooth surface can be made to appear wrinkled. At this time, the lateral dimensions of the concave grooves and the raised areas between the concave grooves are more matched, and the distribution of the concave grooves on the surface of the perovskite film is relatively uniform overall, which can absorb a large amount of incident light and more fully exert the light capture effect of the concave grooves.

[0140] Based on any suitable embodiment in the present application, in some further embodiments, the aspect ratio of at least a portion of the concave grooves is greater than 1, optionally, the aspect ratio of at least a portion of the concave grooves is ≥2, further optionally, the aspect ratio of at least a portion of the concave grooves is ≥3, and further optionally, the aspect ratio of at least a portion of the concave grooves is ≥5. The aspect ratio of at least a portion of the concave grooves can also be any of the following values, or greater than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, etc. See. Figure 1 .

[0141] Figure 1 This is an optical microscope image of the surface morphology of the perovskite film in one embodiment of the present application. The overall distribution of the grooves on the surface of the perovskite film is relatively uniform, and the lateral size combination of the grooves and the raised areas between the grooves is relatively matched, presenting an overall wrinkled morphology.

[0142] By comprehensively adjusting the width and length of the concave grooves, the proportion of the longitudinal projection area of ​​the concave grooves in the longitudinal projection area of ​​the perovskite film can be adjusted. The higher this proportion, the more significant the comprehensive improvement of the overall current level and photoelectric conversion efficiency by the concave grooves. It can be understood that by comprehensively adjusting the width and length of the concave grooves, the aforementioned R1 value can be adjusted. The R1 value is the percentage of the sum of the longitudinal projection areas of the concave grooves relative to the longitudinal projection area of ​​the non-smooth surface.

[0143] Based on any suitable embodiment of the present application, in some further embodiments, the width of at least a portion of the concave grooves may satisfy ≤1.2 μm, and may be 0.5 μm to 1.2 μm, and further may be 0.6 μm to 1.1 μm. The width of at least a portion of the concave grooves may also be selected from any of the following values, or less than or equal to any of the following values, or selected from a range consisting of any two of the following values: 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.15 μm, 1.2 μm, etc.

[0144] Based on any suitable embodiment in the present application, in some further embodiments, the half-height width of at least a portion of the concave grooves can meet ≤1μm, and can be selected from 0.2μm to 0.6μm. The half-height width of at least a portion of the concave grooves can also be selected from any of the following values, or less than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, etc. The half-height width of at least a portion of the concave grooves can also be selected from a suitable range in the following ranges: 0.1μm to 1μm, 0.2μm to 1μm, 0.2μm to 0.7μm, etc.

[0145] Based on any suitable embodiment of the present application, in some further embodiments, the depth of at least a portion of the concave grooves may satisfy ≥100 nm, optionally 100 nm to 500 nm, and further optionally 100 nm to 250 nm. The depth of at least a portion of the concave grooves may also be selected from any of the following values, or greater than or equal to any of the following values ​​(optionally less than or equal to 500 nm), or selected from an interval consisting of any two of the following values: 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 210 nm, 220 nm, 240 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc.

[0146] Based on any suitable embodiment of the present application, in some further embodiments, the aspect ratio of at least a portion of the concave grooves can be 0.08 to 0.5, optionally 0.1 to 0.5, and further optionally 0.1 to 0.3. The aspect ratio of at least a portion of the concave grooves can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.08, 0.1, 0.15, 0.2, 0.22, 0.24, 0.25, 0.26, 0.275, 0.28, 0.30, 0.32, 0.35, 0.36, 0.38, 0.40, 0.42, 0.45, 0.46, 0.48, 0.50, etc.

[0147] Based on any suitable embodiment of the present application, in some further embodiments, the average width of the concave grooves may be 0.2 μm to 1 μm, optionally 0.5 μm to 1.2 μm, and further optionally 0.6 μm to 1.1 μm. The average width of the concave grooves may also be selected from any of the following values, or less than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.15 μm, 1.2 μm, etc. In some embodiments, the average width of at least a portion of the concave grooves may meet the range of 0.6 μm to 1.15 μm.

[0148] Based on any suitable embodiment in the present application, in some further embodiments, the average half-height width of the concave groove can meet ≤1μm, and can be selected from 0.2μm to 0.3μm. The average half-height width of the concave groove can also be selected from any of the following values, or less than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, etc. The average half-height width of the concave groove can also be selected from a suitable range in the following ranges: 0.1μm to 1μm, 0.2μm to 1μm, 0.2μm to 0.7μm, etc.

[0149] Based on any suitable embodiment of the present application, in some further embodiments, the average depth of the concave groove can be 100 nm to 500 nm, optionally 100 nm to 250 nm. The average depth of the concave groove can also be selected from any of the following values, or from an interval consisting of any two of the following values: 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 210 nm, 220 nm, 240 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc.

[0150] Based on any suitable embodiment of the present application, in some further embodiments, the average aspect ratio of the concave groove can be 0.08-0.5, optionally 0.1-0.5, and further optionally 0.1-0.3. The average aspect ratio of the concave groove can also be selected from any of the following values, or from an interval consisting of any two of the following values: 0.08, 0.1, 0.15, 0.2, 0.22, 0.24, 0.25, 0.26, 0.275, 0.28, 0.30, 0.32, 0.35, 0.36, 0.38, 0.40, 0.42, 0.45, 0.46, 0.48, 0.50, etc.

[0151] The width, depth, aspect ratio of the concave trench and the average values ​​of these parameters may be combined in any appropriate manner.

[0152] Based on any suitable embodiment of the present application, in some further embodiments, the concave groove satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0153] The aspect ratio of at least a portion of the concave grooves is greater than 1. Optionally, the aspect ratio of at least a portion of the concave grooves is ≥ 2. Further optionally, the aspect ratio of at least a portion of the concave grooves is ≥ 3. Even further optionally, the aspect ratio of at least a portion of the concave grooves is ≥ 5.

[0154] The width of at least a portion of the concave grooves is ≤1.2 μm, and may be 0.5 μm to 1.2 μm, and may further be 0.6 μm to 1.1 μm;

[0155] The half-height width of at least a portion of the concave grooves is ≤1 μm, and can be optionally 0.2 μm to 0.6 μm;

[0156] The depth of at least a portion of the concave grooves is ≥100 nm, and may be 100 nm to 500 nm, and may further be 100 nm to 250 nm.

[0157] The aspect ratio of at least a portion of the concave grooves is 0.08 to 0.5, optionally 0.1 to 0.5, and further optionally 0.1 to 0.3.

[0158] Based on any suitable embodiment of the present application, in some further embodiments, the concave groove satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0159] In at least a portion of the non-smooth surface, the average width of the concave grooves is 0.2 μm to 1 μm, optionally 0.5 μm to 1.2 μm, and further optionally 0.6 μm to 1.1 μm;

[0160] In at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.1 μm to 1 μm, and can be optionally 0.2 μm to 0.6 μm;

[0161] In at least a portion of the non-smooth surface, the average depth of the concave grooves is 100 nm to 500 nm, and can be optionally 100 nm to 250 nm;

[0162] In at least a portion of the non-smooth surface, the average aspect ratio of the concave grooves is 0.08 to 0.5, optionally 0.1 to 0.5, and further optionally 0.1 to 0.3.

[0163] In the present application, unless otherwise specified, “at least a portion of the concave groove” may be measured in terms of the extended length of the concave groove, and may mean at least 80% of the extended length, or 90% to 100% of the extended length.

[0164] In this application, unless otherwise specified, the "at least a portion of the non-smooth surface" and "at least a portion of the surface of the perovskite film" in the "at least a portion of the non-smooth surface" refer to the non-smooth surface portion or the perovskite film portion corresponding to the projected area area along the longitudinal direction of which the projected area is at least a certain value. "At least a portion of the non-smooth surface" can also be expressed as "the non-smooth surface area corresponding to at least a portion of the projected area of ​​the non-smooth surface along the longitudinal direction". The projected area along the longitudinal direction of at least a portion of the non-smooth surface or at least a portion of the surface of the perovskite film can be ≥0.1mm 2 , further optional ≥0.5mm 2 , further optional ≥0.6mm 2 , non-limiting example such as 960000μm 2 .

[0165] Based on any suitable embodiment of the present application, in some further embodiments, in the non-smooth surface, the concave groove satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0166] The average width of the concave groove is 0.2 μm to 1 μm, optionally 0.5 μm to 1.2 μm, and further optionally 0.6 μm to 1.1 μm;

[0167] The average half-height width of the concave groove is 0.1 μm to 1 μm, and can be optionally 0.2 μm to 0.6 μm;

[0168] The average depth of the concave groove is 100nm to 500nm, and can be optionally 100nm to 250nm;

[0169] The average aspect ratio of the concave groove is 0.08 to 0.5, and may be 0.1 to 0.5, and further may be 0.1 to 0.3.

[0170] By adjusting one or more of the groove's width, depth, aspect ratio, and their average value, the probability of photons being captured by the groove can be adjusted. By controlling one or more of these parameters within the aforementioned ranges, or by controlling multiple parameters in acceptable combinations within the aforementioned ranges, the light-trapping effect of the groove is enhanced, thereby further improving the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0171] Based on any suitable embodiment of the present application, in some further embodiments, in at least a portion of the non-smooth surface, the average spacing of the concave grooves is 1 μm to 20 μm, and can be 10 μm to 20 μm. The average spacing of the concave grooves can also be selected from any of the following values, or from an interval consisting of any two of the following values: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.

[0172] By adjusting the average spacing of the grooves, the density of the grooves in the perovskite film can be adjusted, thereby adjusting the number of grooves. Keeping the average spacing within the above range can fully utilize the aforementioned light-trapping function of the grooves, improving the combined performance of short-circuit current density and photoelectric conversion efficiency.

[0173] Based on any suitable embodiment of the present application, in some further embodiments, at least a portion of the concave grooves have an opening width greater than the bottom width. In some embodiments, based on the projected area of ​​the concave grooves along the longitudinal direction, at least 50% of the concave grooves have an opening width greater than the bottom width. Further optionally, at least 80% of the concave grooves have an opening width greater than the bottom width. The percentage of the sum of the projected areas along the longitudinal direction of the concave grooves that satisfy the requirement of "the opening width of the concave groove is greater than the bottom width" relative to the sum of the projected areas of all concave grooves along the longitudinal direction can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any of the following percentages and 100%, or selected from the interval consisting of any two of the following percentages: 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc. In some embodiments, 100% of the concave grooves have an opening width greater than the bottom width.

[0174] In some embodiments, at least a portion of the concave grooves have an opening width > half-height width > bottom width. In some embodiments, based on the projected area of ​​the concave grooves along the longitudinal direction, at least 50% of the concave grooves have an opening width > half-height width > bottom width. Further optionally, at least 80% of the concave grooves have an opening width > half-height width > bottom width. The percentage of the sum of the projected areas of the concave grooves along the longitudinal direction that satisfy "opening width > half-height width > bottom width" relative to the sum of the projected areas of all concave grooves along the longitudinal direction can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from the interval consisting of any of the following percentages and 100%, or selected from the interval consisting of any two of the following percentages: 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc. In some embodiments, 100% of the concave grooves have an opening width > half-height width > bottom width.

[0175] In the present application, the “at least 50% of the concave grooves” in “based on the projected area of ​​the concave grooves along the longitudinal direction, at least 50% of the concave grooves” means “the concave grooves corresponding to at least 50% of the projected area of ​​the concave grooves along the longitudinal direction”.

[0176] When the concave groove has a cross-sectional shape that is wide at the top and narrow at the bottom, the opening width of the concave groove is greater than the bottom width, which is conducive to more incident light entering the concave groove, thereby improving the absorption of incident light by the perovskite film and increasing the amount of light captured by the concave groove, thereby better improving the comprehensive performance of short-circuit current density and photoelectric conversion efficiency.

[0177] Based on any suitable embodiment of the present application, in some further embodiments, the concave groove satisfies one or more of the following characteristics:

[0178] At least a portion of the concave grooves have corners in their extending directions;

[0179] At least a portion of the concave grooves has a non-linear extension direction;

[0180] At least a portion of the concave grooves have intersection nodes.

[0181] In the present application, “the intersection node between the concave grooves” refers to the intersection position where two concave grooves with different extending directions are connected.

[0182] When at least a portion of the concave grooves have one or more of the following characteristics in the extension direction: (1) there is a corner in the extension direction of at least a portion of the concave grooves; (2) at least a section of the length in the extension direction of at least a portion of the concave grooves is non-linear; and (3) at least a portion of the concave grooves have an intersection node, then the concave grooves are more likely to be randomly distributed on the surface of the perovskite film, which is beneficial to shortening the transmission distance of photons from the contact interface to being captured by the perovskite film, and is beneficial to improving the light capture efficiency, thereby helping to better improve the comprehensive performance of short-circuit current density and photoelectric conversion efficiency. Among them, the existence of "intersection nodes" in different concave grooves means that the extension directions of these different concave grooves are not parallel or not completely parallel, resulting in intersection, so that the different concave grooves are connected.

[0183] Based on any suitable embodiment in the present application, in some further embodiments, the perovskite film includes a titanite-type metal halide, and the halogen in the perovskite-type metal halide includes bromine and iodine.

[0184] According to the composition design of perovskite metal halide in perovskite film, bromine and iodine elements can be set simultaneously in the perovskite precursor solution. By adjusting the ratio of the two elements, multiple parameters such as the size-related parameters of the grooves (such as length, width, depth, aspect ratio and the average value of any of the foregoing) and distribution-related parameters (such as average spacing, the proportion of the groove area on the perovskite film surface, the surface roughness of the perovskite film, etc.) can be controlled, thereby flexibly adjusting the comprehensive enhancement effect of the grooves on the short-circuit current density and photoelectric conversion efficiency.

[0185] In some embodiments, the halogen in the perovskite-type metal halide is bromine and iodine.

[0186] Based on any suitable embodiment of the present application, in some further embodiments, the chemical composition of the perovskite metal halide is ABX3, wherein A is a monovalent cation, B is a divalent cation, and X is a monovalent anion; X in the perovskite metal halide includes Br - and I-.

[0187] As a non-limiting example, A in the perovskite-type metal halide may include one or more of an alkali metal ion, a monovalent amine cation, and a monovalent amidine cation. The alkali metal ion may include Cs + , K + , Rb + 、Li + One or more of .

[0188] Non-limiting examples of monovalent amine cations include (NR 21 R 22 R 23 R 24 ) + 、(R 21 R 22 N=CR 23 R 24 ) + 、(R 21R22 NC(R 25 )=NR 23 R 24 ) + or (R 21 R 22 NC(NR 25 R 26 )=R 23 R 24 ) + , where R 21 、R 22 、R 23 、R 24 、R 25 and R26 Each independently selected from H, C 1-20 alkyl, aryl, substituted C 1-20 alkyl or substituted aryl; wherein, C 1-20 alkyl and substituted C 1-20 In "C 1-20 alkyl" of alkyl and substituted C 1-15 alkyl, it can further be C 1-10 alkyl, still further can be C 1-8 alkyl, still further can be C 1-6 alkyl, still further can be C 1-4 alkyl, still further can be C 1-3 alkyl, still further can be methyl. In "aryl" of aryl and substituted aryl, it can independently be C 6-20 aryl, it can further be C 6-12 aryl, still further can be C 6-10 aryl, still further can be phenyl or naphthyl, still further can be phenyl. Substituents in substituted C 1-20 alkyl and substituted aryl are each independently C 1-10 hydrocarbyl, it can further be C 1-6 alkyl or C 6-10 aryl, still further can be methyl or phenyl.

[0189] Non-limiting examples of monovalent amine cations are CH3NH3 + (methylamine, MA + ), ammonium (NH4 + ). Non-limiting examples of monovalent amidinium cations are NH2CH=NH2 + (formamidine, denoted as FA + ). ]>

[0190] In some embodiments, in the perovskite metal halide, A includes CH(NH2)2 + and Cs + , further, A can be CH(NH2)2 + and Cs + in combination. Non-limitingly, the molar ratio of CH(NH2)2 + and Cs + can be (1-a):a, where 0 < a < 1; a can be selected from any one of the following values, or from any interval formed by any two of the following values: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc., and a can also be selected from the following range: 0.1~0.3, etc.

[0191] As a non-limiting example, B in the perovskite metal halide may include Pb 2+ , Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Zn 2+ , Ge 2+ , Fe 2+ , Co 2+ and Ni 2+ or more than one of them.

[0192] In some embodiments, in the perovskite metal halide, B includes Pb 2+ , and further, B may be Pb 2+ .

[0193] Based on any suitable embodiment in the present application, in some further embodiments, the atomic molar ratio of bromine element to iodine element in the perovskite metal halide is (3 - y):y, where 0 < y ≤ 1.2; optionally, 0.5 ≤ y ≤ 1.2, and further optionally, 0.6 ≤ y ≤ 1.2. Non-limiting examples of y may also include the following values: 0.2, 0.3, 0.4, 0.5, 0.6, 2 / 3, 0.7, 0.75, 0.8, 0.9, 1.0, 1.1, 1.2, etc., and y may also be selected from the intervals formed by any two of the above values.

[0194] According to the composition design of the perovskite metal halide in the perovskite thin film, the atomic molar ratio of bromine element to iodine element in the perovskite precursor solution can be adjusted to improve the comprehensive performance of the short-circuit current density and the photoelectric conversion efficiency of the perovskite solar cell.

[0195] In some embodiments, the perovskite metal halide in the perovskite thin film may be any one of ABX3 in the following Examples 1 - 8.

[0196] Based on any suitable embodiment in the present application, in some further embodiments, the perovskite metal halide satisfies one or more of the following characteristics:

[0197] The halogen in the perovskite metal halide is bromine element and iodine element;

[0198] In the perovskite metal halide, A includes CH(NH2)2 + and Cs + , B includes Pb 2+ , X includes Br - and I - , where CH(NH2)2 + and Cs +The molar ratio is (1 - a):a, where 0 < a < 1; further, a can also be any of the following values, or can also be selected from the intervals formed by any two of the following values: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 2 / 3, 0.7, 0.75, 0.8, 0.9. Non-limiting examples of a are also like 0.1 - 0.3, etc.

[0199] The appropriate perovskite-type metal halide can be selected according to the performance of the perovskite film and the requirements of process control.

[0200] Based on any suitable embodiment in the present application, in some further embodiments, the band gap of the perovskite film can be 1.4 eV - 2.0 eV, and can be optionally 1.6 eV - 1.8 eV.

[0201] In the present application, unless otherwise specified, "band gap" has the well-known meaning in the art, and can be analyzed, compared, and confirmed by conventional methods in the technical field. Non-limitingly, the band gap of a material can be determined by its absorption spectrum or emission spectrum to obtain the band gap parameters, and common optical methods include ultraviolet-visible absorption spectrum, photoluminescence spectrum, and Raman spectrum, etc.

[0202] When the perovskite film has the above band gap, it is beneficial to improve the power density of the device. Combined with the aforementioned concave groove design, it is beneficial to achieve better comprehensive performance of the device.

[0203] Based on any suitable embodiment in the present application, in some further embodiments, at least a part of the perovskite grains in the perovskite film are through-type grains, and both ends of the through-type grains along the longitudinal direction are respectively located on the two side surfaces of the perovskite film.

[0204] In the present application, unless otherwise specified, "through-type grains" refer to through-type grains along the longitudinal direction, which penetrate the thickness of the perovskite film, so that both ends of the through-type grains along the longitudinal direction are respectively located on the two side surfaces of the perovskite film.

[0205] When the perovskite grains in the perovskite film include through-type grains along the thickness direction of the perovskite film (i.e., along the longitudinal direction), it means that these perovskite grains grow continuously in the longitudinal direction, and there are few cracks in the longitudinal cross-section of the perovskite film, presenting as large-sized grains that penetrate longitudinally. At this time, the through-type grains that penetrate the perovskite film longitudinally are beneficial to make the carriers transport more smoothly and efficiently, and are beneficial to reducing the non-radiative recombination caused by grain interfaces, and improving the photoelectric conversion efficiency of the device. A

[0206] Based on any suitable embodiment in the present application, in some further embodiments, the lateral size of at least a part of the through-type grains ≥ 0.4 μm.

[0207] In this application, unless otherwise specified, the "lateral size" of the perovskite grains in the perovskite film refers to the maximum size of the grains in all directions in the transverse cross-section of the film. Statistical analysis can be performed based on the longitudinal and transverse cross-sectional views of the perovskite film. The longitudinal and transverse cross-sectional views of the perovskite film can be obtained by scanning electron microscopy, optical microscopy, and other methods. Based on the grain width in the longitudinal cross-sectional view, a semi-quantitative analysis of the transverse size of the grains can be performed. By analyzing the longitudinal cross-sectional views at different positions and / or in different directions, quantitative statistical analysis data of the transverse size of the grains can also be obtained. Based on the transverse cross-sectional view, quantitative statistics of the transverse size of the grains can be performed.

[0208] In this application, when performing statistical analysis on the grain size in the perovskite film, the amount of data collected is appropriately selected based on the shape, size, uniformity, distribution pattern, etc. of the grains. For example, the minimum amount of data collected can be determined by controlling the standard deviation of the average value to ≤ 10% of the average value.

[0209] Figure 4 This is a scanning electron microscope (SEM) image of a perovskite film in one embodiment of the present application, wherein (A) is a longitudinal cross-sectional view and (B) is a transverse cross-sectional view. As can be seen from the longitudinal cross-sectional view, the perovskite grains in the perovskite film are basically present as longitudinal through-type grains. It can also be seen from the longitudinal cross-sectional view that the transverse dimensions of these through-type grains are relatively large. As can be seen from the transverse cross-sectional view, the proportion of large-sized grains in the perovskite film is relatively large, and the transverse dimensions of each grain can be measured and obtained, thereby performing a statistical analysis of the transverse dimensions of the grains in the perovskite film.

[0210] Without limitation, the lateral dimensions of at least a portion of the through-type grains may also be greater than or equal to any of the following dimensions: 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, etc. In some embodiments, the lateral dimensions of at least a portion of the through-type grains are ≥ 0.6 μm, optionally ≥ 0.8 μm, and further optionally ≥ 1 μm.

[0211] Without limitation, the lateral dimensions of at least a portion of the through-type grains may also be selected from any one of the following sizes or from a range consisting of any two of the following sizes: 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, etc.

[0212] In this application, unless otherwise specified, the term "at least a portion" in "at least a portion of the through-type grains" may be measured by the number of grains, the lateral area of ​​the grains, or the volume of the grains. Using one of the aforementioned measurement methods, "at least a portion" may numerically represent a percentage greater than or equal to any of the following: 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc.

[0213] In some embodiments, the average lateral size of the perovskite grains in the perovskite film is 0.6 μm to 2 μm, and may be 0.6 μm to 1.2 μm. The average lateral size of the perovskite grains in the perovskite film may also be selected from any one of the following sizes or a range consisting of any two of the following sizes: 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, etc.

[0214] By controlling the lateral size of the through-grains, the number of interfaces between perovskite grains can be adjusted. A larger lateral size reduces the number of through-grains, resulting in fewer defects and higher-quality perovskite films. By controlling the lateral size of the through-grains within the aforementioned range, the positive effects of the through-grains can be fully utilized.

[0215] In some embodiments, the average lateral size of the through-type grains is 0.6 μm to 2 μm, and can be 0.6 μm to 1.2 μm. The average lateral size of the through-type grains can also be selected from any one of the following sizes or a range consisting of any two of the following sizes: 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, etc.

[0216] By controlling the lateral size of the through-grains, the number of interfaces between perovskite grains can be adjusted. A larger lateral size reduces the number of through-grains, resulting in fewer defects and higher-quality perovskite films. By controlling the lateral size of the through-grains within the aforementioned range, the positive effects of the through-grains can be fully utilized.

[0217] Based on any suitable embodiment of the present application, in some further embodiments, in a longitudinal cross-section of the perovskite film, the area percentage of the through-type grains with a lateral size of 1 μm or greater relative to the longitudinal cross-section is ≥30%, optionally ≥40%, and further optionally ≥50%. The area percentage of the through-type grains with a lateral size of 1 μm or greater relative to the longitudinal cross-section can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from a range consisting of any two of the following percentages: 30%, 35%, 40%, 45%, 50%, etc.

[0218] By controlling the percentage of the area occupied by larger through-type grains in the longitudinal cross-section of the perovskite film, the role of the through-type grains can be adjusted. By controlling the area percentage of through-type grains with a certain lateral size (e.g., lateral size ≥ 1μm) relative to the longitudinal cross-section of the perovskite film within the above range, the advantages of the through-type grains can be more fully utilized, which is more conducive to improving carrier transport and photoelectric conversion efficiency.

[0219] Based on any suitable embodiment of the present application, in some further embodiments, in a transverse cross-section of the perovskite film, the area percentage of the perovskite grains with a lateral size of 1 μm or greater relative to the non-smooth surface is ≥40%, optionally ≥50%, and further optionally ≥60%. The area percentage of the perovskite grains with a lateral size of 1 μm or greater relative to the non-smooth surface can also be selected from any of the following percentages, or greater than or equal to any of the following percentages, or selected from a range consisting of any two of the following percentages: 40%, 45%, 50%, 55%, 60%, etc.

[0220] By controlling the area percentage of larger perovskite grains in the transverse cross-section of the perovskite film, it is beneficial to reduce film defects, improve film quality, and enhance photoelectric conversion efficiency.

[0221] In a second aspect of the present application, a perovskite cell is provided, comprising the perovskite film according to the first aspect of the present application, wherein the non-smooth surface in the perovskite film forms a non-smooth interface with an adjacent structural layer.

[0222] In the present application, the non-smooth surface in the perovskite film may be placed on the emission side of the incident light.

[0223] When the perovskite film described in the first aspect of the present application is used as a light-absorbing layer in a perovskite cell, it can also be called a perovskite layer.

[0224] Based on any suitable embodiment of the present application, in some further embodiments, the non-smooth surface of the perovskite film is located on the side from which incident light exits. In this case, when incident light enters the perovskite film and exits from the non-smooth surface, the reflection effect of the concave grooves on light can be used to allow more photons that have exited the perovskite film to re-enter the perovskite film.

[0225] Based on any suitable embodiment in the present application, in some further embodiments, the present application provides a perovskite battery, which includes an electron transport layer, a hole transport layer and the perovskite film described in the first aspect of the present application, wherein the perovskite film is arranged between the electron transport layer and the hole transport layer.

[0226] Based on any suitable embodiment in the present application, in some further embodiments, the non-smooth surface in the perovskite film is located on a side close to the electron transport layer.

[0227] Based on any suitable embodiment of the present application, in some further embodiments, the hole transport layer is located between the first electrode and the perovskite layer, and the electron transport layer is located between the second electrode and the perovskite layer. In other embodiments, the electron transport layer is located between the first electrode and the perovskite layer, and the hole transport layer is located between the second electrode and the perovskite layer.

[0228] Based on any suitable embodiment in the present application, in some further embodiments, the present application provides a perovskite battery, which includes a positive electrode, a negative electrode and the perovskite film described in the first aspect of the present application, wherein the perovskite film is arranged between the positive electrode and the negative electrode.

[0229] In this application, unless otherwise specified, the perovskite film in the perovskite cell can be disassembled and the film surface tested and analyzed in the following manner: Taking the electron transport layer as C60 / BCP and the second electrode located on the surface of the electron transport layer away from the light absorbing layer as an example, the perovskite cell can be disassembled, the second electrode (such as the Cu electrode) removed, and the electron transport layer (such as C60 / BCP) can be washed away using the antisolvent of the corresponding perovskite film (such as chlorobenzene). The second electrode can be removed by, for example, removing it with tape.

[0230] Based on any suitable embodiment of the present application, in some further embodiments, the present application provides a perovskite battery, which includes a positive electrode, an electron transport layer, the perovskite film described in the first aspect of the present application, a hole transport layer, and a negative electrode arranged in sequence. Further, it can be any of an inverted PIN battery and a formal NIP battery.

[0231] When a perovskite cell is operating, after the light-absorbing layer is exposed to light, the electrons inside gain energy and break free from the constraints of the light-absorbing layer to form negatively charged electron carriers. At the same time, positively charged hole carriers are formed, thereby forming electron-hole pairs. The free electrons and free holes are transmitted in opposite directions through the corresponding transport layers, causing the electrons and holes to flow, forming an electric current and realizing the conversion of light energy into electrical energy. Furthermore, after the perovskite layer absorbs photons, it is stimulated to produce electron-hole pairs. The electron-hole pairs further dissociate to form free carriers with opposite charges. The free electrons are transmitted to the positive electrode through the electron transport layer, and the free holes are transmitted to the negative electrode through the hole transport layer. The two free carriers are collected by the corresponding electrodes, further forming a photocurrent in the perovskite cell circuit.

[0232] The electron transport layer can extract and transport electron carriers and block the passage of free holes.

[0233] The hole transport layer can extract and transport hole carriers and block the passage of free electrons.

[0234] It is understood that the perovskite battery further comprises two electrodes, one of which serves as a positive electrode to collect electron carriers transported via the electron transport layer, and the other serves as a negative electrode to collect hole carriers transported via the hole transport layer.

[0235] Based on any suitable embodiment of the present application, in some further embodiments, the electron transport material in the electron transport layer may include but is not limited to one or more of the following materials and their derivatives: imide compounds, quinone compounds, fullerenes and their derivatives, methoxytriphenylamine-fluoroformamidine (OMeTPA-FA), calcium titanate (CaTiO3), lithium fluoride (LiF), calcium fluoride (CaF2), poly (3,4-ethylenedioxythiophene): polystyrene sulfonic acid (PEDOT:PSS), poly 3-hexylthiophene (P3HT), triptycene as the core Triphenylamine (H101), 3,4-ethylenedioxythiophene-methoxytriphenylamine (EDOT-OMeTPA), N-(4-phenylamino)carbazole-spirobifluorene (CzPAF-SBF), polythiophene, metal oxides, silicon oxide (SiO2), strontium titanate (SrTiO3), cuprous thiocyanate (CuSCN), etc.; wherein the metal elements may include one or more of Mg, Ni, Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga and Cr.

[0236] Based on any suitable embodiment of the present application, in some further embodiments, the electron transport material in the electron transport layer may include but is not limited to one or more of the following materials: bathocuproine, [6,6]-phenyl-C 61-Isomethyl butyrate, [6,6]-phenyl C 71 -Methyl butyrate, C 60 、C 70 , tin oxide (SnO x , the value of x can range from 1.5 to 2), zinc oxide and its derivatives, and modified products of any of the above materials after doping or passivation.

[0237] Based on any suitable embodiment of the present application, in some further embodiments, the hole transport material in the hole transport layer may include but is not limited to one or more of the following materials and their derivatives: 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), polytriarylamine (PTAA), nickel oxide (NiO x ), poly 3,4-ethylenedioxythiophene: polystyrene sulfonic acid (PEDOT:PSS), WO3 and other materials can transport holes and block electrons.

[0238] Based on any suitable embodiment in the present application, in some further embodiments, the hole transport material in the hole transport layer may include but is not limited to [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly-3-hexylthiophene, triphenylamine with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine, N-(4-phenylamino)carbazole-spirobifluorene, poly(3,4-ethylenedioxythiophene): poly(styrenesulfonic acid), polythiophene, nickel oxide, molybdenum oxide, Cuprous iodide, cuprous oxide and its derivatives, or one or more of doped or passivated [4-(3,6-dimethoxy-9H-carbazol-9-yl)butyl]phosphonic acid, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly-3-hexylthiophene, triphenylamine with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine, N-(4-anilino)carbazole-spirobifluorene, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid), polythiophene, nickel oxide, molybdenum oxide, cuprous iodide, cuprous oxide, carbazole phosphate, etc.

[0239] Based on any suitable embodiment of the present application, in some further embodiments, the perovskite cell 100 includes Figure 7 The structure shown includes a substrate layer 110, a first electrode 120, a first charge transport layer 130, a perovskite layer 140, a second charge transport layer 150, and a second electrode 160, which are arranged in sequence. Furthermore, the structural layers shown in the figure are stacked in sequence.

[0240] Based on any suitable embodiment of the present application, in some further embodiments, one of the "first charge transport layer" and the "second charge transport layer" is an electron transport layer and the other is a hole transport layer. In some embodiments, the first charge transport layer is an electron transport layer. In some embodiments, the first charge transport layer is a hole transport layer.

[0241] Based on any appropriate embodiment in the present application, in some further embodiments, at least one of the “first electrode” and the “second electrode” is a transparent electrode.

[0242] Based on any suitable embodiment of the present application, in some further embodiments, one of the "first electrode" and the "second electrode" is a transparent electrode for light incident. In some embodiments, the first electrode is a transparent electrode. Based on any suitable embodiment of the present application, in some further embodiments, the non-smooth surface of the perovskite film faces away from one of the transparent electrodes. In this case, incident light from the transparent electrode strikes the perovskite film and then exits through the non-smooth surface. The reflection of light by the concave grooves can be used to allow more photons that exit the perovskite film to re-enter the perovskite film. In addition, the perovskite film can be formed on a substrate containing a transparent electrode. In this case, from a process perspective, fewer subsequent steps are required from forming the non-smooth surface to producing the perovskite cell, minimizing the impact on the performance of the perovskite layer. A non-limiting example of a substrate containing a transparent electrode includes a substrate containing a transparent electrode comprising a transparent electrode, a first charge transport layer, and a perovskite film stacked in sequence. The first charge transport layer can be a hole transport layer or an electron transport layer. In some examples, the first charge transport layer is a hole transport layer. Furthermore, a substrate layer is provided on the side of the transparent electrode facing away from the perovskite film.

[0243] Based on any suitable embodiment of the present application, in some further embodiments, the transparent conductive material contained in the transparent electrode may include a conductive oxide. Without limitation, the conductive oxide may include one or more of indium tin oxide, fluorine-doped tin oxide, indium-doped tungsten oxide, indium-doped zinc oxide, and aluminum-doped zinc oxide.

[0244] Based on any suitable embodiment in the present application, in some further embodiments, the material of the transparent electrode may be exemplified by, but not limited to, one or more of the following materials: FTO (fluorine-doped tin oxide), ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), BZO (boron-doped zinc oxide), IZO (indium zinc oxide), IWO (tungsten-doped indium oxide), etc.

[0245] Based on any suitable embodiment in the present application, in some further embodiments, one of the first electrode and the second electrode comprises a conductive material, and optionally, the second electrode comprises the conductive material. The conductive material may be an organic conductive material, an inorganic conductive material, or a combination thereof. Non-limiting examples of inorganic conductive materials include metal conductive materials. Further, the metal conductive material may include any one of gold (Au), silver (Ag), copper (Cu), aluminum (Al), nickel (Ni), chromium (Cr), bismuth (Bi), platinum (Pt), magnesium (Mg), etc., or any suitable mixture of the foregoing elements. The conductive material may include a conductive oxide. Further, the conductive material may be a conductive oxide; non-limiting examples of conductive oxides may include one or more of FTO, ITO, IWO, AZO, etc.

[0246] Based on any suitable embodiment of the present application, in some further embodiments, one of the first electrode and the second electrode is a metal electrode, and optionally, the second electrode is a metal electrode. The metal electrode may include one or more of gold (Au), silver (Ag), copper (Cu), aluminum (Al), nickel (Ni), chromium (Cr), bismuth (Bi), platinum (Pt), magnesium (Mg), molybdenum (Mo), tungsten (W), etc.

[0247] Based on any suitable embodiment of the present application, in some further embodiments, the perovskite cell includes a first electrode, a first charge transport layer, a perovskite layer, a second charge transport layer, and a second electrode arranged in sequence;

[0248] Wherein, the perovskite layer is the perovskite film described in the first aspect of this application;

[0249] One of the first charge transport layer and the second charge transport layer is an electron transport layer, and the other is a hole transport layer;

[0250] At least one of the first electrode and the second electrode is a transparent electrode;

[0251] The non-smooth surface in the perovskite film faces away from one of the transparent electrodes.

[0252] The first electrode may be a transparent electrode. The second electrode may also be a transparent electrode. The first electrode and the second electrode may both be transparent electrodes. In this case, the non-smooth surface of the perovskite film may face either the first electrode or the second electrode.

[0253] In some embodiments, the perovskite cell includes a substrate layer. The substrate may be disposed at the first electrode or at the second electrode. In some embodiments, the perovskite cell includes a substrate layer, a first electrode, a first charge transport layer, a perovskite layer, a second charge transport layer, and a second electrode disposed in sequence. In some embodiments, the perovskite cell includes a substrate layer, a second electrode, a second charge transport layer, a perovskite layer, a first charge transport layer, and a first electrode disposed in sequence.

[0254] The substrate layer involved in the embodiments or examples of this application can be, but is not limited to, a glass substrate or a flexible substrate. Without limitation, the flexible substrate can include one or more materials selected from polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, and polyethylene naphthalate. Optionally, the first electrode is a transparent electrode for light incidence.

[0255] Based on any suitable embodiment of the present application, in some further embodiments, the base layer is a flexible base layer. Further, the material of the base layer can be, for example, (but not limited to) an organic polymer material, and further, can be a mixture of one or more of the following materials in different proportions: including but not limited to polyvinyl alcohol (PVA), polyester (PET), polyimide (PI), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), etc.

[0256] Based on any suitable embodiment in the present application, in some further embodiments, the perovskite cell is any one of an inverted pin cell and a formal nip cell.

[0257] The perovskite cells provided in this application can be either formal or trans.

[0258] In some embodiments, the perovskite cell has a pin structure.

[0259] Based on any suitable embodiment in the present application, in some further embodiments, the perovskite cell includes a transparent electrode and an electron transport layer, a perovskite layer, a hole transport layer and a second electrode sequentially stacked on the transparent electrode.

[0260] Based on any suitable embodiment of the present application, in some further embodiments, for the trans configuration, the perovskite cell includes a transparent electrode and a hole transport layer, a perovskite layer, an electron transport layer, and a second electrode sequentially stacked on the transparent electrode, wherein the transparent electrode is used for light incidence and serves as a first electrode.

[0261] Based on any suitable embodiment in the present application, in some further embodiments, the perovskite cell includes the following structures arranged in sequence: a substrate layer (which can be a glass substrate or a flexible substrate), a first electrode, a hole transport layer, a perovskite layer, an electron transport layer and a second electrode.

[0262] Based on any suitable embodiment of the present application, in some further embodiments, the perovskite cell comprises the following structure arranged in sequence: a substrate layer (glass substrate or flexible substrate), a first electrode, an electron transport layer, a perovskite layer, a hole transport layer, and a second electrode. Optionally, the first electrode is a transparent electrode for light incidence. The definition of flexible substrate can be found above.

[0263] In some embodiments, the perovskite cell is provided with three cross-layer etching regions, P1, P2, and P3. The etching region group consisting of the P1 etching region, the P2 etching region, and the P3 etching region is used to divide the perovskite cell into a number of sub-cells connected in series. Each sub-cell includes a P1 etching region, a P2 etching region, and a P3 etching region arranged in sequence, and the P2 etching region is located between the P1 etching region and the P3 etching region. The P1 etching region, the P2 etching region, and the P3 etching region can respectively connect the structural layers that are set apart, so that the structural layer between the first electrode and the second electrode forms a loop, and the perovskite cell is formed into a perovskite cell component. P1, P2, and P3 can each independently be a linear etching region, also called an etching line. P1, P2, and P3 can each independently be a laser etching region. The number of P1, P2, and P3 corresponds to the number of sub-cells. Without limitation, P1, P2 and P3 can be arranged as follows: P1 is used to divide the first electrode, with its two ends connected to the first charge transport layer and the base layer respectively; P2 is used to penetrate and divide the second charge transport layer, the perovskite layer and the first charge transport layer, with the two ends of the P2 etching area connected to the second electrode and the first electrode respectively; P3 is used to penetrate and divide the second electrode, the second charge transport layer, the perovskite layer and the first charge transport layer, with one end of P3 connected to the surface of the first electrode and the other end passing through the outer surface of the second electrode.

[0264] In some embodiments, the perovskite cell comprises Figure 8 The structure shown (a vertical cross-sectional structure diagram of the device) includes a substrate layer 110, a first electrode 120, a first charge transport layer 130, a perovskite layer 140, a second charge transport layer 150 and a second electrode 160 stacked in sequence. Three etching regions P1, P2 and P3 are also provided to divide the perovskite cell into several sub-cells connected in series. P1 is used to divide the first electrode, P2 is used to penetrate and divide the second charge transport layer, the perovskite layer and the first charge transport layer, and P3 is used to penetrate and divide the second electrode, the second charge transport layer, the perovskite layer and the first charge transport layer.

[0265] In some embodiments, Figure 8 The base layer 110 in the structure shown is a light-incident glass base.

[0266] In some embodiments, the filling material in the P1 etched region of the perovskite cell may be consistent with the first charge transport layer.

[0267] In some embodiments, the filling material in the P2 etched region of the perovskite cell may be consistent with the second electrode.

[0268] In some embodiments, the width of P1 is 10 μm to 50 μm, for example, 30 μm.

[0269] In some embodiments, the width of P2 is 10 μm to 200 μm, for example, 150 μm. Furthermore, the distance between P2 and P1 can be 20 μm to 80 μm, for example, 20 μm.

[0270] In some embodiments, the width of P3 is 10 μm to 50 μm, for example, 15 μm. Furthermore, the distance between P3 and P2 can be 20 μm to 40 μm, for example, 20 μm.

[0271] The specifications of the perovskite cell are not particularly limited and may be, but not limited to, 300 mm×300 mm.

[0272] It is understood that the structure of the perovskite cell involved in this application may not be limited to the structural layers listed above. Other functional layers, such as buffer layers and insertion layers, may also be introduced as needed. In some embodiments, the perovskite cell may be provided with a buffer layer of suitable energy level, which may play one or more of the following roles: reducing the energy barrier, promoting energy level matching, improving carrier extraction efficiency, passivating interface defect states, protecting the light absorption layer, inhibiting the oxidation and decomposition of water molecules and oxygen in the cell, improving the photoelectric conversion efficiency, and improving the stability of the perovskite cell. Depending on the location of the buffer layer, the types of buffer layers may include four types: a buffer layer between the hole transport layer and the anode, a buffer layer between the electron transport layer and the cathode, a buffer layer between the hole transport layer and the absorption layer, and a buffer layer between the electron transport layer and the absorption layer. Materials that can be used for the buffer layer in the perovskite cell may include, but are not limited to, Cu2O, NiO, AZO, TiO2, etc. In some embodiments, an insertion layer may be provided between the electron transport layer and the second electrode. An example of the material of the insertion layer is bathocuproine (BCP).

[0273] A glass knife can be used to cut the perovskite cell sample longitudinally, and the longitudinal cross section can be pointed upward for morphological observation, such as SEM testing.

[0274] The perovskite film can also be sliced ​​longitudinally along the thickness direction of the perovskite cell to obtain a longitudinal cross-section, which can then be combined with elemental analysis methods to analyze the elemental composition and content. For example, this can be tested and analyzed by combining continuous longitudinal sectioning with a cryo-focused electron beam (FIB), cross-sectional SEM morphology observation, energy dispersive spectroscopy (EDS) elemental spectroscopy, and 3D reconstruction analysis software.

[0275] In a third aspect of the present application, a method for preparing a perovskite battery is provided, which can be used to prepare the perovskite battery described in the second aspect of the present application.

[0276] In some embodiments, a method for preparing a perovskite battery is provided, comprising the steps of: sequentially stacking a first charge transport layer, a perovskite layer, a second charge transport layer, and a second electrode on a surface of a first electrode to obtain the perovskite battery; wherein the perovskite layer is a perovskite film as defined in the first aspect of the present application;

[0277] The method of stacking the perovskite layer on the side of the first charge transport layer facing away from the first electrode comprises the following steps:

[0278] Applying a precursor solution of the perovskite layer to a surface of the first charge transport layer facing away from the first electrode;

[0279] The precursor liquid is subjected to vacuum flash evaporation treatment and annealing treatment to form the perovskite layer; the aforementioned non-smooth surface can be formed on a side of the perovskite layer away from the first electrode.

[0280] The vacuum flash evaporation process, used to prepare the perovskite layer, creates the aforementioned concave groove structure on at least one surface of the perovskite layer, increasing light utilization and improving the combined performance of the perovskite cell's short-circuit current density and photoelectric conversion efficiency. Furthermore, it promotes the formation of large, through-hole grains, boosting carrier transport and photoelectric conversion efficiency.

[0281] Based on any suitable embodiment of the present application, in some further embodiments, the solvent in the precursor solution of the perovskite layer includes N,N-dimethylformamide and dimethyl sulfoxide;

[0282] Optionally, the solvent in the precursor solution of the perovskite layer is a combination of N,N-dimethylformamide and dimethyl sulfoxide;

[0283] Optionally, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (2-6):1, and further optionally (3-5):1.

[0284] Based on any suitable embodiment of the present application, in some further embodiments, the preparation method satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0285] The vacuum flash evaporation treatment is carried out under negative pressure conditions, wherein the pressure of the negative pressure conditions is ≤100Pa, and can be selected from 60Pa to 100Pa;

[0286] The duration of the vacuum flash evaporation treatment is 15s to 100s, and can be optionally 20s to 60s;

[0287] The temperature for the vacuum flash treatment is 20°C to 40°C, and can be optionally 20°C to 30°C;

[0288] The annealing treatment is performed using a hot plate, optionally using a hot plate at 90°C to 110°C, further optionally using a hot plate at 95°C to 105°C;

[0289] The annealing time for the annealing treatment is 5 minutes to 20 minutes, and can be optionally 8 minutes to 12 minutes.

[0290] The negative pressure condition may be, but is not limited to, 60 Pa to 100 Pa, and may also be selected from any one of the following pressures or an interval consisting of any two of the following pressures: 60 Pa, 70 Pa, 80 Pa, 90 Pa, etc.

[0291] The temperature for the vacuum flash evaporation treatment may be, but is not limited to, 10°C to 40°C, and may also be selected from any one of the following temperatures or a range consisting of any two of the following temperatures: 10°C, 15°C, 16°C, 18°C, 20°C, 22°C, 25°C, 30°C, 35°C, 40°C, etc. The temperature for the vacuum flash evaporation treatment may also be in the following ranges: 18°C ​​to 30°C, 18°C ​​to 25°C, 18°C ​​to 22°C, etc.

[0292] The duration of the vacuum flash treatment can be, but is not limited to, 15s to 100s, and can also be selected from any of the following durations or an interval consisting of any two of the following durations: 15s, 20s, 25s, 30s, 35s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, etc.

[0293] Based on any suitable embodiment of the present application, in some further embodiments, the coating method in the step of coating the precursor solution of the perovskite layer onto the surface of the first charge transport layer on the side away from the first electrode is spin coating;

[0294] Optionally, the spin coating speed is 2000 rpm to 6000 rpm, and optionally 2000 rpm to 4000 rpm.

[0295] By adjusting one or more parameters in the perovskite layer preparation process and regulating the grain size and surface morphology of the perovskite layer as needed, the comprehensive performance of the short-circuit current density and photoelectric conversion efficiency of the perovskite battery can be better improved through process parameter optimization.

[0296] Each structural layer other than the perovskite layer in the perovskite cell can be prepared by one or more of the following methods, including but not limited to: chemical bath deposition, electrochemical deposition, chemical vapor deposition, thermal evaporation co-evaporation, atomic layer deposition, magnetron sputtering, precursor liquid spin coating, precursor liquid slit coating, precursor liquid blade coating, mechanical pressing, etc. A suitable method can be selected according to the material properties of each structural layer to be stacked with the adjacent structural layer. In some embodiments, each structural layer other than the perovskite layer in the perovskite cell can be prepared by one or more of the following methods, including but not limited to: thermal evaporation, precursor liquid coating, etc., wherein the precursor liquid coating method can be a precursor liquid spin coating method.

[0297] In some embodiments, a perovskite cell is prepared using a method comprising the following steps:

[0298] S10: P1 etching on the first electrode: P1 etching is performed on the FTO conductive glass laminated on the glass substrate to expose the glass substrate, thereby obtaining a first substrate, wherein the FTO serves as the first electrode and the base layer serves as the glass substrate. The first charge transport layer can be prepared after cleaning.

[0299] For example, consider 20 sheets of 2.0 cm x 2.0 cm FTO conductive glass. P1 laser etching is used to remove 0.35 cm of FTO from each end, exposing the glass substrate. The etched FTO conductive glass is then ultrasonically cleaned several times using a cleaning solution, deionized water, and ethanol. The FTO conductive glass is then blown dry with a nitrogen gun to remove the solvent and then placed in a UV ozone generator for further cleaning.

[0300] S20: preparing a first charge transport layer: spin-coating a solution containing a hole transport material on the first electrode side surface of the first substrate, and annealing under heating conditions to form a hole transport layer.

[0301] The thickness of the hole transport layer may be 2 nm to 20 nm.

[0302] Non-limiting examples are as follows: On an FTO substrate after ultraviolet ozone treatment, a solution containing a hole transport material is spin-coated at a rate of 2000 rpm in a glove box and annealed on a hot plate at 100 °C for 10 min to form a hole transport layer. The hole transport material can be a self-assembled molecular solution of 0.5 mg / mL, and the solvent can be isopropanol. Non-limiting examples of self-assembled molecules include, for example, MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid), 2PACz ([2-(9H-carbazol-9-yl)ethyl]phosphonic acid), 4PACz ([4-(9H-carbazol-9-yl)butyl]phosphonic acid), 6PACz ([2-(9h-carbazol-9-yl)hexyl]phosphonic acid), Me-4PACz ([4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid), Me-2PACz ([(3,6-dimethyl-9h-carbazol-9-yl)butyl]phosphonic acid), etc., and one or more carbazole phosphate molecules.

[0303] S30: Prepare a perovskite layer: Spin-coat a perovskite precursor solution on the hole transport layer, perform vacuum flash evaporation treatment, and then anneal under heating conditions to form a perovskite thin film (also denoted as the perovskite layer).

[0304] It can be understood that when the size of the perovskite battery is suitable, such as some small-sized perovskite batteries, the etching step in the preparation process of the perovskite battery can also be omitted.

[0305] Non-limiting examples are as follows: Spin-coat a perovskite precursor solution on the hole transport layer at 2000 rpm to 6000 rpm, then place it in a vacuum flash evaporation device for 20 s to 60 s, and transfer it to a hot plate at 100 °C for annealing for 10 min to form a perovskite layer. Among them, the perovskite precursor solution includes a perovskite precursor material, and the perovskite precursor material includes a monovalent cation A, a divalent cation B, and a monovalent anion X. The solvent can be a mixed solvent of DMF and DMSO with a volume ratio of (2 to 6):1.

[0306] The perovskite precursor solution can be prepared by the following method: According to the stoichiometric ratio of the perovskite-type metal halide in the perovskite layer, dissolve the perovskite precursor material in a solvent to form a mixed solution, stir for 1 h, and filter with a 0.22 μm organic filter membrane to obtain the perovskite precursor solution. Taking the perovskite-type metal halide as Cs a FA 1-a PbI 3-y Br y (0 < a < 1, 0 < y ≤ 1.2) as an example, the perovskite precursor material can be a combination of lead iodide, lead bromide, formamidinium bromide, formamidinium iodide, cesium iodide, and cesium bromide, and the active substance of the perovskite absorption layer is the CsFA system.

[0307] S40: preparing a second charge transport layer and a second electrode: sequentially evaporating an electron transport layer and a second electrode on the perovskite layer.

[0308] Non-limiting example: using an evaporation machine to deposit an electron transport layer (C 60 ), an insertion layer (BCP), and a second electrode (Cu) with thicknesses of 25 nm, 8 nm, and 100 nm, respectively, to obtain a perovskite cell. The first charge transport layer, the perovskite layer, and the second charge transport layer constitute the photoelectric conversion layer.

[0309] After the electron transport layer is formed, P2 etching is performed to a depth of the first electrode surface close to the hole transport layer. The formed P2 etching splits the photoelectric conversion layer. Figure 8 .

[0310] After forming the second electrode, perform P3 etching to a depth of the first electrode surface close to the hole transport layer. The formed P3 etching separates the photoelectric conversion layer and the second electrode. Figure 8 .

[0311] In the fourth aspect of the present application, an electrical device is provided, which includes at least one of the perovskite film described in the first aspect of the present application, the perovskite battery described in the second aspect of the present application, and the perovskite battery prepared by the preparation method described in the third aspect of the present application.

[0312] In some embodiments, the perovskite cell can be used as a power generation device in an electrical device. The type of power generation device can include, but is not limited to, an integrated power generation device. The location of the power generation device can include, but is not limited to, the roof or back panel of a vehicle.

[0313] Furthermore, the above-mentioned electrical devices may include mobile devices, such as mobile phones, laptop computers, etc., electric vehicles, electric trains, ships and satellites, power generation systems, etc., but are not limited thereto.

[0314] Figure 9 The power consumption device 6 is an automobile, and can further be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0315] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, a calculator, etc.

[0316] As another example, the power-consuming device may be a wearable device, such as a watch.

[0317] Below, some embodiments of the present application are described. The embodiment described below is exemplary, is only used to explain the present application, and cannot be construed as limiting the present application. In the embodiment, if no technology or conditions are indicated, it is carried out according to the description above, or according to the technology or conditions described in the document in this area or according to the product specification. Reagents used or instruments that are not indicated by the manufacturer are conventional products that can be obtained commercially, or can be synthesized in a conventional manner by commercially available products.

[0318] In the following examples, room temperature refers to 20°C to 30°C.

[0319] Preparation method of perovskite battery: vacuum flash evaporation method to prepare perovskite layer

[0320] S10: P1 Etching on the First Electrode: P1 etching is performed on the FTO conductive glass laminated on the glass substrate, exposing the glass substrate to obtain a first substrate, in which the FTO serves as the first electrode and the base layer serves as the glass substrate. The etched FTO conductive glass is ultrasonically cleaned several times using a cleaning solution, deionized water, and ethanol, in sequence. The FTO conductive glass is blown dry with a nitrogen gun to remove the solvent and then placed in a UV ozone generator for further cleaning.

[0321] S20: Preparation of the first charge transport layer: On the UV-ozone treated FTO substrate, a solution containing a hole transport material was spin-coated at 2000 rpm in a glove box. The solution was annealed on a 100°C hot plate for 10 minutes to form a hole transport layer. The hole transport material was a 0.5 mg / mL solution of self-assembled molecules (MeO-2PACz) in isopropyl alcohol.

[0322] S30: Preparation of perovskite layer: Spin-coat the perovskite precursor liquid on the hole transport layer at 4000 rpm, then place it in a vacuum flash evaporation device, vacuum flash evaporation for 30 seconds at 20°C and 70Pa, transfer it to a 100°C hot stage for annealing for 10 minutes to form a perovskite layer. The perovskite precursor liquid includes a perovskite precursor material, which is a combination of lead iodide, lead bromide, bromoformamidine, iodoformamidine, cesium iodide and cesium bromide. The active material of the perovskite absorption layer is the CsFA system, and the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 4:1. The corresponding perovskite metal halide is Cs a FA 1-a PbI 3-y Br y (0 <a<1,0<y≤1.2)。

[0323] The perovskite precursor solution was prepared by the following method: according to the stoichiometric ratio of the perovskite-type metal halide in the perovskite layer, the perovskite precursor material was dissolved in a solvent to form a mixed solution, stirred for 1 hour, and filtered with a 0.22 μm organic filter membrane to obtain the perovskite precursor solution.

[0324] S40: Evaporate an electron transport layer (C 60 ), an interlayer (BCP), and a second electrode (Cu) on the perovskite layer, with thicknesses of 25 nm, 8 nm, and 100 nm respectively, to obtain a perovskite solar cell.

[0325] In Example 1, the vacuum flash evaporation treatment parameters for preparing the perovskite layer were vacuum flash evaporation treatment for 30 s under the conditions of 20 °C and 70 Pa, and Cs a FA 1-a PbI 3-y Br y (0 < a < 1, 0 < y ≤ 1.2), where a was 0.2 and y was 1.2.

[0326] In Examples 2 - 8, perovskite solar cells were prepared using substantially the same method as in Example 1. The only difference was the composition of the perovskite metal halide. The preparation parameters can be referred to in Table 1.

[0327] Among them, in Examples 2 - 5, the y value in Cs a FA 1-a PbI 3-y Br y in the shown ABX3 was adjusted, and in Examples 6 - 7, the a value in Cs a FA 1-a PbI 3-y Br y was adjusted.

[0328] In Example 8, a perovskite solar cell was prepared using substantially the same method as in Example 1, except that: the type of the perovskite metal halide ABX3 was changed. The difference between Example 8 and Example 1 was that: A in ABX3 was replaced with C s0.1 FA 0.8 MA[[ID=4,5]] 0.1 , and ABX3 was C s0.1 FA 0.8 MA 0.1 PbI 3-y Br y .

[0329] Comparative Examples 1 - 3. Preparation of the perovskite layer by the anti-solvent method

[0330] In Comparative Example 1, the same perovskite precursor solution as in Example 1 was used, but the anti-solvent method was adopted for preparation; Comparative Examples 2 - 3 adjusted the y value based on Comparative Example 1. The perovskite metal halide in the perovskite precursor solution can be referred to in Table 1.

[0331] S10: P1 Etching on the First Electrode: P1 etching is performed on the FTO conductive glass laminated on the glass substrate to expose the glass substrate, obtaining the first substrate. The FTO serves as the first electrode, and the base layer is the glass substrate. The etched FTO conductive glass is ultrasonically cleaned several times successively with cleaning solution, deionized water, and ethanol. The FTO conductive glass is dried with a nitrogen gun to remove the solvent and then further cleaned in an ultraviolet ozone machine.

[0332] S20: Preparation of the First Charge Transport Layer: On the FTO substrate after ultraviolet ozone treatment, a solution containing a hole transport material is spin-coated at a rate of 2000 rpm in a glove box and annealed on a hot plate at 100 °C for 10 min to form a hole transport layer. The hole transport material is a 0.5 mg / mL MeO-2PACz solution, and the solvent is isopropanol.

[0333] S30: Preparation of the Perovskite Layer: The perovskite precursor solution is spin-coated on the hole transport layer at 2000 rpm - 6000 rpm for a total of 50 s. At the 30th second, 200 μL of chlorobenzene solution is dropped in. After spin-coating, the film is transferred to a hot plate at 100 °C and annealed for 10 min to form the perovskite layer. Among them, the perovskite precursor solution includes perovskite precursor materials, which are a combination of lead iodide, lead bromide, bromomethylammonium, iodomethylammonium, cesium iodide, and cesium bromide. The active substance of the perovskite absorption layer is the CsFA system, and the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 4:1. The corresponding perovskite-type metal halide is Cs a FA 1- a PbI 3-y Br y (0 < a < 1, 0 < y ≤ 1.2). The elemental composition of the perovskite-type metal halide can be referred to Table 1.

[0334] The perovskite precursor solution is prepared by the following method: According to the stoichiometric ratio of the perovskite-type metal halide in the perovskite layer, the perovskite precursor materials are dissolved in the solvent to form a mixed solution, stirred for 1 h, and filtered with a 0.22 μm organic filter membrane to obtain the perovskite precursor solution.

[0335] S40: Evaporate the electron transport layer (C60), the interlayer (BCP), and the second electrode (Cu) on the perovskite layer with an evaporation machine, with thicknesses of 25 nm, 8 nm, and 100 nm respectively, to obtain a perovskite solar cell.

[0336] Comparative Example 4 - 5 uses a method basically the same as that of Example 1, and the differences are referred to Table 1.

[0337] Comparative Example 4: A perovskite solar cell is prepared using a method basically the same as that of Example 1, except that X in ABX3 is only bromine and y = 3.

[0338] In Comparative Example 5, a perovskite cell was prepared using a method substantially the same as that in Example 1, except that X in ABX3 was only iodine, and y=0.

[0339] In Comparative Example 6, a perovskite cell was prepared using a method substantially the same as that in Example 1, except that the vacuum flash evaporation treatment temperature was changed from 20°C to 50°C.

[0340] Comparative Example 7 uses a method basically the same as Example 1 to prepare a perovskite cell, except that the type of perovskite metal halide ABX3 is changed, and FA is replaced by MA.

[0341] Comparative Example 8 uses a method similar to that of Example 1 to prepare a perovskite battery, except that the type of perovskite metal halide ABX3 is changed, and Pb as B is replaced by Pb 0.5 Sn 0.5 .

[0342] Table 1.

[0343]

[0344]

[0345] Test analysis methods

[0346] 1. Morphology and structure testing

[0347] Samples with deposited perovskite thin films were fixed to a sample holder using conductive tape for SEM testing. A scanning electron microscope (SEM) is an experimental observation method intermediate between a transmission electron microscope and an optical microscope. It uses an electron beam to scan the surface of the sample being observed. The electron beam then collects a series of electronic signals generated by the interaction between the electron beam and the sample, converts them, amplifies them, and digitally processes them to form an image. It offers a large depth of field, a wide field of view, and excellent three-dimensional imaging, making it effective for analyzing the sample's surface morphology. By varying the scanning amplitude of the electron beam across the sample surface, the magnification can be varied. Test samples can be observed at magnifications ranging from approximately 20x to 200,000x, such as 7K, 10K, 20K, and 30K, with 1K = 1000x. The SEM can be used to observe the crystallization of perovskite samples (such as grain size, grain thickness, and the presence of through-type grains with lateral dimensions ≥ 1μm) and their morphological characteristics.

[0348] SEM test object: A thin film component with a perovskite film deposited on a hole transport layer but not yet deposited with an electron transport layer can be tested and analyzed in both the vertical and horizontal directions.

[0349] (1) The observation surface is the exposed side of the perovskite layer.

[0350] (2) Cut a 1×0.5 cm piece of the prepared perovskite film using a glass cutter 2 The film was glued onto the SEM sample preparation table with the longitudinal section facing upwards, and the crystal quality and grain thickness were observed using SEM.

[0351] Based on the SEM image of the longitudinal section, it can also be combined with analysis software such as Image-J to obtain relevant information such as "the area ratio of through-type grains with a lateral size of ≥1μm in the longitudinal section".

[0352] 2. Analysis of surface roughness and structural dimensions of perovskite films.

[0353] A step profiler (probe profilometer) was used to test the surface roughness and groove structure of the perovskite film.

[0354] Sample to be tested: A thin film component in which a perovskite layer has been deposited on a hole transport layer but an electron transport layer has not yet been deposited (step S30 has been completed and step S40 has not yet been performed), with one side of the perovskite layer being used as the test surface.

[0355] Test conditions: The probe directly contacts the surface to record the profile change, which can obtain the two-dimensional profile change and calculate the line roughness.

[0356] The test is conducted using a contact-motion method: When the stylus slides gently along the surface being tested, the stylus moves up and down along the tiny peaks and valleys on the surface. The motion trajectory of the stylus reflects the surface contour.

[0357] Test results and analysis methods: A surface topography curve (also known as a surface roughness curve) can be obtained. The "valleys" in the curve correspond to concave grooves, and the area between the two nearest peaks with a fluctuation depth ≥100nm is considered a "valley". By counting the "valley depth" in the surface roughness curve, the surface roughness of the surface to be tested can be obtained. Further analysis can be performed to obtain dimensional parameters such as the width, average width, length, aspect ratio, half-height width, average half-height width, depth, average depth, aspect ratio, and average aspect ratio of the concave grooves. In addition, these dimensional parameters of the concave grooves can also be obtained by observing and analyzing SEM images of longitudinal cross-sections at certain magnifications, such as magnifications of 20K, 30K, and 40K.

[0358] 3. Optical microscope observation

[0359] Test sample: A thin-film device with a perovskite layer deposited on a hole transport layer but not yet deposited with an electron transport layer (step S30 completed, step S40 not yet performed). The perovskite layer side surface serves as the test surface. The lateral dimension of the device is designated as A2.

[0360] Instrument: Optical microscope (Keyence VHX-S650E). The perovskite film was placed directly under the light beam and the focus was adjusted for observation.

[0361] Sample to be tested: A thin film component in which a perovskite layer has been deposited on a hole transport layer but an electron transport layer has not yet been deposited (step S30 has been completed and step S40 has not yet been performed), with one side of the perovskite layer being used as the test surface.

[0362] Test analysis method:

[0363] Select at least 960000μm 2 Statistical analysis was performed within the area.

[0364] (1) A surface morphology image of the perovskite film can be obtained. The area enclosed by the outline of the concave groove in the image is recorded as A1, and the "percentage of the sum of the projected areas of the concave grooves along the longitudinal direction relative to the projected area of ​​the non-smooth surface along the longitudinal direction (recorded as R1)" = A1 / A2×100%.

[0365] (2) The average spacing of the grooves can be obtained by measuring the spacing between multiple adjacent grooves based on the center line analysis of the groove width and taking the average value.

[0366] 4. Perovskite battery performance test

[0367] The perovskite battery to be tested is connected to a dedicated capacitor and used as a variable load. During the process of the perovskite battery charging the capacitor, current and voltage samples are sampled, and the corresponding current and voltage data are recorded and plotted into a volt-ampere characteristic curve (IV curve). The various electrical performance parameters are calculated to obtain the test values ​​of open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and photoelectric conversion efficiency (PCE).

[0368] Photoelectric conversion efficiency is calculated as follows: PCE = Pout / Popt

[0369] =Voc×Jsc×(Vmpp×Jmpp) / (Voc×Jsc)

[0370] =Voc×Jsc×FF

[0371] Among them, Pout, Popt, Vmpp, and Jmpp are the battery operating output power, incident light power, battery maximum power point voltage, and maximum power point current, respectively.

[0372] The test and analysis results can be found in Tables 2 and 3.

[0373] Test result analysis:

[0374] Figure 1This is an optical microscope image of the surface morphology of the perovskite film prepared by the vacuum flash evaporation method in Example 1 of the present application. In this image, the overall distribution of the grooves on the surface of the perovskite film is relatively uniform, and the lateral size combination of the raised areas between the grooves is relatively matched, presenting a wrinkled morphology as a whole.

[0375] from Figure 1 It can also be seen that the aspect ratio of most of the concave grooves is greater than 1, and meets a variety of aspect ratio ranges, including but not limited to concave grooves meeting the following aspect ratios: ≥2, ≥3, ≥5, etc.

[0376] from Figure 1 It can also be seen that some of the concave grooves have corners in their extension direction. Some of the concave grooves have non-straight lines in their extension direction. Some adjacent concave grooves have intersection nodes, that is, some adjacent concave grooves are connected through the intersection nodes.

[0377] Figure 2 This is a comparison chart of the surface roughness tests of the perovskite films prepared in Example 1 and Comparative Example 1 of the present application. The horizontal axis is the test track along the horizontal direction, which is recorded as "horizontal track". Among them, the vacuum flash evaporation method corresponds to Example 1, and the anti-solvent method corresponds to Comparative Example 1. It can be seen that the surface of the perovskite film in Example 1 prepared by the vacuum flash evaporation method is a non-smooth surface with a certain degree of roughness; while the surface of the perovskite film in Comparative Example 1 prepared by the anti-solvent method is relatively smooth as a whole. According to Figure 1 , we can also analyze and obtain the "percentage of the sum of the projected areas of the concave grooves along the longitudinal direction relative to the projected area of ​​the non-smooth surface along the longitudinal direction (which can be recorded as R1)" and the average spacing of the concave grooves.

[0378] according to Figure 2 It can be seen that the depth of the concave groove is mainly between 100nm and 250nm, and the half-height width is mainly between 200nm and 600nm; in addition, the width, average width, half-height width, average half-height width, depth, average depth, aspect ratio, average aspect ratio and other parameters of the concave groove can also be analyzed and obtained, which can be summarized in Table 2-3.

[0379] from Figure 2 It can also be seen that the opening width of some concave grooves is greater than the bottom width. The opening width of some concave grooves is greater than the half-height width and the bottom width.

[0380] Figure 3 This is a graph showing the volt-ampere characteristic of the perovskite film prepared by the vacuum flash evaporation method in Example 1 of the present application. It can be seen that the short-circuit current density of Example 1 is higher than that of Comparative Example 1, and the battery efficiency of Example 1 is higher than that of Comparative Example 1.

[0381] Figure 4This is a scanning electron microscope (SEM) image of the perovskite film prepared by the vacuum flash evaporation method in Example 1 of the present application, wherein (A) is a longitudinal cross-sectional view and (B) is a transverse plane view.

[0382] Figure 5 Scanning electron microscope (SEM) images of the perovskite film prepared by the anti-solvent method in Comparative Example 1 of this application, where (A) is a longitudinal cross-sectional view and (B) is a transverse plan view. The perovskite film formed in Comparative Example 1 has a relatively smooth surface, is essentially free of longitudinally penetrating grains, and has a relatively small grain size.

[0383] Figure 6 This is a statistical bar chart of the grain size of the perovskite thin films prepared in Example 1 and Comparative Example 1 of the present application, wherein a is Example 1, which adopts the vacuum flash evaporation method, and b is Comparative Example 1, which adopts the anti-solvent method. Figure 6 Statistics are performed based on the maximum diameter of perovskite film grains within the statistical range.

[0384] according to Figure 4 and Figure 6 In b, in the perovskite film prepared by the vacuum flash evaporation method in Example 1, the perovskite crystal quality is high, the average size of the perovskite grains in the perovskite layer is large, and there are few defects. Figure 4 The longitudinal cross-sectional view in Figure A shows that the perovskite film prepared in Example 1 has few cracks along the longitudinal cross-section, forming longitudinally penetrating grains. Some of these penetrating grains have a lateral size of 1 μm or greater. The percentage of penetrating grains with a lateral size of 1 μm or greater relative to the area of ​​the longitudinal cross-section is greater than 40%. Figure 4 In the transverse cross-sectional view of Figure B, a large number of large perovskite grains can be observed in the perovskite layer of Example 1, and the lateral size of the grains can reach 1μm to 2μm. Figure 4 Middle B and Figure 6 In middle b, the area percentage of perovskite grains with lateral size ≥ 1 μm relative to the non-smooth surface is high.

[0385] according to Figure 5 and Figure 6 In a, in the perovskite film prepared by the anti-solvent method in Comparative Example 1, the average size of the perovskite grains is relatively small and the film has many defects. Figure 5 Many broken crystals were observed in the longitudinal cross section A, but there were basically no penetrating grains. That is, most of the grains were difficult to penetrate the film in the longitudinal direction, which easily hindered the carrier transport process. Figure 5 The lateral size of the grains in the transverse cross-sectional view of Figure B is significantly smaller than that in Example 1. Figure 4 Transverse dimensions of grains in the transverse cross-section in Figure B.

[0386] In each of the examples (Examples 1-8), concave grooves with an aspect ratio greater than 1 were present within the test area, and they met various aspect ratio ranges, including but not limited to grooves meeting the following aspect ratios: ≥2, ≥3, ≥5, etc. Furthermore, the width of the concave grooves primarily ranged from ±0.1 μm of the average width, the depth primarily ranged from ±10 nm or ±5 nm of the average depth, and the aspect ratio primarily ranged from ±0.03, ±0.02, or ±0.01 of the average aspect ratio.

[0387] The surfaces of the perovskite films in Comparative Examples 1-8 are all relatively flat surfaces, with basically no concave groove structures. Among them, Comparative Example 1 uses the same perovskite precursor solution as Example 1, but is prepared by the anti-solvent method; Comparative Examples 2-3 adjust the y value based on Comparative Example 1 and are also prepared by the anti-solvent method. The halogen X in the perovskite metal halide in Comparative Example 4 is only bromine element (y=3), and the halogen X in the perovskite metal halide in Comparative Example 5 is only iodine element (y=0). The vacuum flash evaporation treatment temperature in Comparative Example 6 is relatively high (50°C). Comparative Example 7 replaces the monovalent cation A in the perovskite metal halide from FA to MA. Comparative Example 8 replaces the divalent cation B in the perovskite metal halide from Pb element to Pb 0.5 Sn 0.5 .

[0388] Table 2.

[0389]

[0390] In Examples 1-8, the average depth of the grooves and the surface roughness in the test area are substantially equal in value.

[0391] Table 3.

[0392]

[0393] In Table 3, R1 represents the percentage of the sum of the projected areas of the concave grooves along the longitudinal direction relative to the projected area of ​​the non-smooth surface along the longitudinal direction.

[0394] The above description of the various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced with each other and will not be repeated herein for the sake of brevity.

[0395] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0396] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical idea and exerting the same effects are all included in the technical scope of the present application. The above-mentioned embodiments only express several embodiments of the present application, and the description thereof is relatively detailed, but it cannot be understood as limiting the scope of the patent. In addition, without departing from the scope of the subject matter of the present application, other methods of applying various modifications that can be thought of by those skilled in the art to the embodiments and combining some of the constituent elements in the embodiments to construct the embodiments are also included in the scope of the present application.

Claims

1. A perovskite film, wherein the thickness direction of the perovskite film is recorded as a longitudinal direction, and the perovskite film has two surfaces that are separated from each other along the longitudinal direction, characterized in that: At least one surface is a non-smooth surface, and the non-smooth surface is provided with a plurality of concave grooves; At least a portion of the side surfaces of the concave groove are inclined at an angle relative to the longitudinal direction.

2. The perovskite film according to claim 1, characterized in that The surface roughness of the non-smooth area formed by at least a portion of the concave grooves is greater than or equal to 100 nm, Optionally, the surface roughness of the non-smooth area formed by at least a portion of the concave grooves is 100 nm to 250 nm; Optionally, the surface roughness is obtained by testing using a step profiler method.

3. The perovskite thin film according to claim 1 or 2, characterized in that: The percentage of the sum of the projection areas of the concave grooves along the longitudinal direction to the projection area of ​​the non-smooth surface along the longitudinal direction is greater than or equal to 10%, and can be optionally greater than or equal to 30%, and can further be optionally greater than or equal to 50%.

4. The perovskite thin film according to any one of claims 1 to 3, characterized in that The concave groove meets one or more of the following characteristics: The aspect ratio of at least a portion of the concave grooves is greater than 1. Optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 2. Further optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 3. Further optionally, the aspect ratio of at least a portion of the concave grooves is greater than or equal to 5. The width of at least a portion of the concave grooves is less than or equal to 1.2 μm, and may be 0.5 μm to 1.2 μm, and may be 0.6 μm to 1.1 μm. The half-height width of at least a portion of the concave grooves is less than or equal to 1 μm, and can be optionally 0.2 μm to 0.6 μm; The depth of at least a portion of the concave grooves is greater than or equal to 100 nm, and may be 100 nm to 500 nm, and may be further 100 nm to 250 nm; The aspect ratio of at least a portion of the concave grooves is 0.08 to 0.5, can be 0.1 to 0.5, and can further be 0.1 to 0.

3.

5. The perovskite thin film according to any one of claims 1 to 4, characterized in that The concave groove meets one or more of the following characteristics: In at least a portion of the non-smooth surface, the average width of the concave groove is 0.2 μm to 1 μm, optionally 0.5 μm to 1.2 μm, and further optionally 0.6 μm to 1.1 μm; In at least a portion of the non-smooth surface, the average half-height width of the concave groove is 0.1 μm to 1 μm, and can be 0.2 μm to 0.6 μm; In at least a portion of the non-smooth surface, the average depth of the concave groove is 100nm to 500nm, and can be 100nm to 250nm; In at least a portion of the non-smooth surface, the average aspect ratio of the concave grooves is 0.08 to 0.5, can be 0.1 to 0.5, and can further be 0.1 to 0.

3.

6. The perovskite thin film according to any one of claims 1 to 5, characterized in that In at least a portion of the non-smooth surface, an average interval between the concave grooves is 1 μm to 20 μm, and may be 10 μm to 20 μm.

7. The perovskite thin film according to any one of claims 1 to 6, characterized in that The opening width of at least a portion of the concave grooves is greater than the bottom width; Optionally, based on the projected area of ​​the concave grooves along the longitudinal direction, at least 50% of the opening widths of the concave grooves are greater than the bottom widths, and further optionally, at least 80% of the opening widths of the concave grooves are greater than the bottom widths; Optionally, based on the projected area of ​​the concave groove along the longitudinal direction, at least a portion of the concave grooves has an opening width > half-height width > bottom width; further optionally, at least 50% of the concave grooves have an opening width > half-height width > bottom width; further optionally, at least 80% of the concave grooves have an opening width > half-height width > bottom width.

8. The perovskite thin film according to any one of claims 1 to 7, characterized in that The concave groove meets one or more of the following characteristics: At least a portion of the concave grooves have corners in their extending directions; At least a portion of the concave grooves have a non-linear extension direction; At least a portion of the concave grooves have intersection nodes.

9. The perovskite thin film according to any one of claims 1 to 8, characterized in that The perovskite film includes perovskite-type metal halide, and the halogen in the perovskite-type metal halide includes bromine and iodine.

10. The perovskite thin film according to claim 9, characterized in that: The atomic molar ratio of bromine element to iodine element in the perovskite-type metal halide is (3-y):y, wherein 0 <y≤1.2; Optionally, 0.6≤y≤1.

2.

11. The perovskite thin film according to any one of claims 1 to 10, characterized in that The band gap of the perovskite film is 1.4 eV to 2.0 eV, and can be optionally 1.6 eV to 1.8 eV.

12. The perovskite thin film according to any one of claims 1 to 11, characterized in that At least a portion of the perovskite grains in the perovskite film are through-type grains, and two ends of the through-type grains along the longitudinal direction are respectively located on two side surfaces of the perovskite film.

13. The perovskite thin film according to any one of claims 1 to 12, characterized in that The lateral dimension of at least a portion of the through-type grains is greater than or equal to 0.4 μm; wherein the lateral direction is orthogonal to the longitudinal direction; Optionally, a lateral dimension of at least a portion of the through-type grains is greater than or equal to 0.6 μm, optionally greater than or equal to 0.8 μm, and further optionally greater than or equal to 1 μm; Optionally, the average lateral size of the through-type grains is 0.6 μm to 2 μm, and optionally 0.6 μm to 1.2 μm.

14. The perovskite thin film according to any one of claims 1 to 13, characterized in that On the longitudinal cross section of the perovskite film, the area percentage of the through-type grains with a lateral size greater than or equal to 1 μm relative to the longitudinal cross section is greater than or equal to 30%, optionally greater than or equal to 40%, and further optionally greater than or equal to 50%.

15. A perovskite battery, characterized in that: The perovskite film comprises the perovskite film according to any one of claims 1 to 14, wherein the non-smooth surface in the perovskite film forms a non-smooth interface with an adjacent structural layer.

16. The perovskite cell according to claim 15, characterized in that: It includes a first electrode, a first charge transport layer, a perovskite layer, a second charge transport layer and a second electrode which are arranged in sequence; Wherein, the perovskite layer is the perovskite film according to any one of claims 1 to 14; One of the first charge transport layer and the second charge transport layer is an electron transport layer, and the other is a hole transport layer; At least one of the first electrode and the second electrode is a transparent electrode; The non-smooth surface in the perovskite film faces away from one of the transparent electrodes.

17. A method for preparing a perovskite battery, characterized in that: The method comprises the following steps: sequentially stacking a first charge transport layer, a perovskite layer, a second charge transport layer and a second electrode on a surface of one side of a first electrode to prepare the perovskite battery; wherein the perovskite layer is a perovskite film as defined in any one of claims 1 to 14; The method of stacking the perovskite layer on the side of the first charge transport layer away from the first electrode comprises the following steps: Applying a precursor solution of the perovskite layer onto a surface of the first charge transport layer facing away from the first electrode; The precursor liquid is subjected to vacuum flash evaporation treatment and annealing treatment to form the perovskite layer, and the non-smooth surface is formed on a side of the perovskite layer away from the first electrode.

18. The preparation method according to claim 17, characterized in that: The solvent in the precursor solution of the perovskite layer includes N,N-dimethylformamide and dimethyl sulfoxide; Optionally, the solvent in the precursor solution of the perovskite layer is a combination of N,N-dimethylformamide and dimethyl sulfoxide; Optionally, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (2-6):1, and further optionally is (3-5):

1.

19. The preparation method according to claim 17 or 18, characterized in that: The preparation method meets one or more of the following characteristics: The vacuum flash treatment is carried out under negative pressure conditions, the pressure of the negative pressure conditions is less than or equal to 100 Pa, and can be selected from 50 Pa to 100 Pa; The duration of the vacuum flash treatment is 15s to 100s, and can be optionally 20s to 60s; The temperature for the vacuum flash treatment is 10°C to 40°C, and can be further 20°C to 30°C; The annealing treatment is performed by a hot stage, optionally, a 90°C to 110°C hot stage, further optionally, a 95°C to 105°C hot stage; The annealing time for the annealing treatment is 5 minutes to 20 minutes, and can be optionally 8 minutes to 12 minutes.

20. The preparation method according to any one of claims 17 to 19, characterized in that: The coating method in the step of coating the precursor solution of the perovskite layer onto the surface of the first charge transport layer on the side away from the first electrode is spin coating; Optionally, the spin coating rotation speed is 2000 rpm to 6000 rpm, and further optionally 2000 rpm to 4000 rpm.

21. An electrical device, characterized in that: The invention comprises at least one of the perovskite film according to any one of claims 1 to 14, the perovskite battery according to claim 15 or 16, and the perovskite battery prepared by the preparation method according to any one of claims 17 to 20.

Citation Information

Cited By

  • Perovskite thin film, perovskite cell, preparation method, electric device and power generation device

    EP4797915A1